Absorbent article including a lower acquisition and distribution system - Patents.com

The introduction of a lower acquisition and distribution system in absorbent articles addresses liquid distribution issues by confining liquids away from the wearer's skin, ensuring a dry surface and reducing vapor penetration, thereby improving comfort and extending wear time.

JP7617106B2Active Publication Date: 2025-01-17PROCTER & GAMBLE CO
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2022532683
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-11
Filing Date
2020-12-07
Publication Date
2025-01-17
Estimated Expiration
2040-12-07

AI Technical Summary

Technical Problem

Existing absorbent articles suffer from liquid distribution issues, leading to a cold, damp feeling on the garment-facing surface due to vapor penetration and liquid accumulation near the backsheet, which can cause discomfort and premature changes.

Method used

Incorporation of a lower acquisition and distribution system between the absorbent material and the backsheet to confine liquids away from the wearer's skin and clothing, utilizing a non-woven layer to temporarily store and reabsorb excess liquid, minimizing the amount of liquid adjacent to the backsheet.

Benefits of technology

The solution effectively reduces the liquid volume near the backsheet, maintaining a dry wearer-facing surface while preventing vapor penetration, enhancing comfort and reducing the need for premature diaper changes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007617106000015
    Figure 0007617106000015
  • Figure 0007617106000016
    Figure 0007617106000016
  • Figure 0007617106000017
    Figure 0007617106000017
Patent Text Reader

Abstract

An absorbent article comprising a topsheet, a backsheet, and a layer of absorbent material sandwiched between the topsheet and the backsheet, the layer of absorbent material (28) comprising a superabsorbent polymer. The absorbent article further comprises a lower acquisition and distribution system having at least one nonwoven or woven layer, the lower acquisition and distribution system being sandwiched between the layer of absorbent material and the backsheet. The absorbent article has a first zone corresponding to 800 μm, originating from and including the topsheet and extending toward the backsheet, and a second zone corresponding to 800 μm, originating from and including the backsheet and extending toward the topsheet. The amount of liquid in the first and second zones is very small as measured by the NMR test method described herein.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention provides an absorbent article for personal hygiene, such as a diaper or pants (for babies, toddlers or adults). The absorbent article includes a lower acquisition and distribution system between a backsheet and a layer of absorbent material, and optionally an upper acquisition and distribution system between a topsheet and a layer of absorbent material. The absorbent article has only a small amount of liquid in the area adjacent to the topsheet and adjacent to the backsheet, when measured according to the Nuclear Magnetic Resonance (NMR)-based test method described herein. [Background technology]

[0002] Absorbent articles for babies, toddlers and adults are well known and widely used. Absorbent articles such as diapers and pants typically have a topsheet and a backsheet between which an absorbent core is provided. Body fluids such as urine are transported through the topsheet into the absorbent article and are eventually absorbed and stored in the absorbent material of the absorbent core. Typical absorbent materials are cellulosic fibers (often called "fluff pulp" or "airfelt" in the context of absorbent articles), absorbent foams, absorbent synthetic fibers or superabsorbent materials. Commonly used superabsorbent materials are superabsorbent polymers, which are typically provided as particles but may take the form of superabsorbent polymer fibers or superabsorbent polymer foams.

[0003] An additional acquisition and distribution system (hereinafter referred to as "ADS") is often provided between the absorbent core and the topsheet. Such a system may be made of one or more layers of material. For example, the ADS may have an acquisition layer in direct contact with the topsheet, which mainly contributes to the rapid acquisition of fluids from the topsheet to avoid free liquids on the topsheet that may result in leakage. An additional layer may be applied under and in direct contact with the acquisition layer (distribution layer). The distribution layer may mainly contribute to the distribution of fluids in the plane of the layer to provide a more uniform liquid distribution throughout the absorbent article. The distribution layer may be in direct contact with the absorbent core. Both layers also function as reservoirs to temporarily hold liquids before they are finally stored in the absorbent core. Alternatively, the ADS may be made of a single layer providing both acquisition and distribution functions.

[0004] Thus, an ADS disposed between the topsheet and the absorbent core can help reduce leakage of bodily fluids in the form of free-flowing liquids on the topsheet that can leak out of the absorbent article and adversely affect skin health.

[0005] However, there is also a risk that the liquid may not be absorbed into the absorbent core quickly enough and therefore may flow through the absorbent core onto the backsheet. Particularly in situations where a high gush volume is delivered to the absorbent article in just a few seconds, the ADS between the absorbent core and the topsheet may not have enough void volume to temporarily hold the liquid before it can be absorbed and stored in the absorbent material of the absorbent core. Particularly when the absorbent core has a relatively high percentage of superabsorbent polymer material, the absorption of the liquid into the superabsorbent polymer material may not be fast enough to handle relatively large amounts of liquid in a satisfactory manner (particularly when the superabsorbent polymer material is not pre-wetted, i.e. when there is an initial gush of liquid in the article, the superabsorbent polymer material typically absorbs liquid more slowly than a pure airfelt layer).

[0006] Although backsheets are generally liquid impermeable, moisture or liquid vapor trapped between the absorbent core and the backsheet can still penetrate the backsheet, resulting in a cold, wet, uncomfortable feeling when the backsheet is touched from the outside (e.g., by a caregiver). This effect is further increased when a breathable backsheet is used. Such a wet feeling is not only uncomfortable, but can also lead to premature diaper changes, long before the absorbent article's absorption capacity is exhausted.

[0007] Another concern arises from liquids that are stored in the air felt between the superabsorbent polymers, rather than in the superabsorbent polymer material (in the case of absorbent cores made with a mixture of air felt and superabsorbent polymer material). This liquid also tends to be present in the region of the absorbent core close to the backsheet. Vapors of such liquids can also penetrate the backsheet and produce the same effect of a cool, clammy feel as outlined in the previous paragraph.

[0008] Furthermore, in addition to the damp, cold feeling that can result when vapor penetrates the backsheet, the presence of liquid in the absorbent article close to the backsheet also creates an unpleasant feeling when the absorbent article is touched from the outside. This is not due (only) to evaporation or migration through the film, but because the thermal conductivity of liquid is generally much higher than that of air or a relatively dry rock structure with air present in the gaps and voids. For example, liquid freshly provided to the absorbent article may initially feel warm to the outside, but after a certain time, this changes to feel somewhat cool to the outside when touched from the outside.

[0009] Finally, liquids such as urine that remain near the backsheet can result in increased visibility of soiling from the outside through the backsheet. Summary of the Invention [Problem to be solved by the invention]

[0010] Therefore, there is a need for an absorbent article that addresses the above problems. It is therefore an object of the present invention to provide an absorbent article that can reduce or eliminate the cold, wet garment-facing surface of the backsheet while at the same time providing a dry, wearer-facing surface. [Means for solving the problem]

[0011] Absorbent articles are typically constructed with a focus on "confining liquid away" from the wearer's skin. As a result, it is often found that liquid is distributed in the absorbent article such that the majority of the liquid is stored toward and adjacent to the backsheet. Furthermore, an acquisition and distribution system (ADS) is typically provided only between the topsheet and the absorbent core, which contributes to the rapid transport of liquid away from the wearer's skin and to maintaining a dry absorbent article surface facing the wearer (i.e., the topsheet). As a result, as described above, vapor and moisture may penetrate the (liquid-impermeable, but often breathable) backsheet. To address these shortcomings, the inventors have found that liquid should not only be transported and confined away from the wearer's skin, but should also be stored deep inside the absorbent article, i.e., away from both the wearer- and garment-facing surfaces.

[0012] As a result, an absorbent article is provided having a lower ADS. The lower ADS acts as an additional layer between the layer of absorbent material and the backsheet. In this way, liquid adjacent to the surface of the layer of absorbent material facing towards the backsheet is not in direct contact with the backsheet. Furthermore, liquid that would otherwise penetrate the backsheet, for example in a gush situation where a relatively large amount of liquid is transported into the absorbent article in a very short time, can be captured and temporarily retained by the lower ADS and then reabsorbed into the layer of absorbent material for eventual containment.

[0013] The inventors have tested a number of absorbent articles currently on the market to determine how liquid is distributed in the absorbent article in the thickness direction, i.e. how much liquid is stored near the topsheet and how much liquid is stored near the backsheet. For this purpose, NMR technology is used and a test method has been established that allows the provision of an accurate liquid distribution profile. This method was chosen due to its non-destructive nature and because it fully reflects the real use conditions of absorbent articles. The general NMR test method and equipment are described in US Pat. Nos. 10,371,652 and 10,365,237. Based on the general principles of the NMR test procedure, an optimized distribution profile has been developed, which is obtained by the use of a suitable lower ADS that reduces the amount of liquid in the backsheet direction to below a threshold of less than 80 μl, i.e. to 0.08 ml (summing up the liquid amounts measured at three different positions and following the test protocol described herein). Similarly, the amount of liquid in the topsheet direction is very low, i.e. less than 90 μl. All these liquid volumes correspond to a measurement area of ​​1.9 cm x 1.9 cm and a measurement depth of 800 μm (i.e. 0.0008 m).

[0014] The present invention also provides an absorbent article comprising: a topsheet, a backsheet, and a layer of absorbent material sandwiched between the topsheet and the backsheet, the layer of absorbent material comprising a superabsorbent polymer; a lower acquisition and distribution system having at least one woven or preferably nonwoven layer, said lower acquisition and distribution system being sandwiched between a layer of absorbent material and a backsheet; - optionally an upper acquisition and distribution system having at least one layer, the upper acquisition and distribution system being sandwiched between the layer of absorbent material and the topsheet.

[0015] The layer of absorbent material may consist of a single layer or may include two or more sublayers, which may be the same or different from one another, for example, in size, composition, thickness, or a combination thereof.

[0016] The absorbent article has a first zone corresponding to 800 μm (i.e., 0.0008 m) originating from and including the topsheet and extending toward the backsheet, and a second zone corresponding to 800 μm originating from and including the backsheet and extending toward the topsheet.

[0017] The absorbent article is subjected to the NMR MOUSE method described herein to determine and sum the amount of liquid at three defined locations to have a total liquid amount of less than 90 μl, or less than 80 μl, or less than 75 μl in the first zone and a total liquid amount of less than 80 μl or less than 75 μl in the second zone.

[0018] For the total amount of liquid in the first or second zone, the amount of liquid is measured at three defined locations: at the fill point (i.e., the location where the liquid was introduced into the absorbent article for NMR testing), 4 cm away from the fill point toward the rear waist region on the longitudinal centerline, and 8 cm away from the fill point toward the rear waist region on the longitudinal centerline. The amounts measured at these three locations are added and the sum is reported as the "total amount of liquid" in the first or second zone.

[0019] Additionally, the amount of liquid at the fill point of the first zone as measured by the NMR MOUSE test method described herein may be 50 μl or less, or 40 μl or less, or 35 μl or less. The amount of liquid at the fill point of the second zone as measured by the NMR MOUSE test method described herein may be 50 μl or less, or 40 μl or less, or 35 μl or less.

[0020] Thus, in the absorbent article of the present invention, liquid is retained on the inside of the absorbent article with only a small amount of liquid remaining in areas adjacent the inner, wearer-facing surface as well as the outer, garment-facing surface of the absorbent article.

[0021] The liquid distribution within the absorbent article is measured by using the NMR MOUSE (Nuclear Magnetic Resonance Mobile Universal Surface Explorer) methodology. The NMR MOUSE is a portable device that uses an open NMR sensor to characterize the positioning of fluids within a porous media structure (i.e., an absorbent article). This method allows for accurate determination of liquid distribution.

[0022] For the present invention, the NMR MOUSE technique is used to determine the amount of liquid in the first zone and the second zone. For this, two liquid jets are introduced into the absorbent article according to the detailed test protocol described below. For smaller absorbent articles, a smaller amount of liquid is used in the test method compared to larger absorbent articles in order to better reflect the use conditions of absorbent articles of different sizes (due to the lower overall liquid capacity of smaller absorbent articles, see details below). The amount of liquid in the first zone and the second zone is measured by NMR MOUSE. This amount is measured at the fill point (i.e. the area where the liquid is introduced into the absorbent article), 4 cm away from the fill point on the longitudinal centerline of the absorbent article towards the rear waist region, and 8 cm away from the fill point on the longitudinal centerline of the article towards the rear waist region. The liquid amounts at these three locations are summed up. This sum is the total liquid amount reported by this test method, but the liquid amount at the fill point, i.e., excluding the liquid amount 4 cm and 8 cm away from the fill point, is reported as "liquid amount at fill point."

[0023] According to the present invention, in the first zone, there are three locations (combined) that have a total of less than 90 μl, or less than 80 μl, or less than 75 μl of liquid as determined by the NMR MOUSE test method described herein. Also, in the second zone, there are three locations (combined) that have a total of less than 80 μl, or less than 75 μl of liquid as determined by the NMR MOUSE test method described herein. To illustrate the order of magnitude reflected by less than 90 μl and less than 80 μl of liquid, respectively, the test method protocol calls for a total of 150 ml to be introduced in two equal successive spurts into a relatively large sized absorbent article, and a total of 80 ml to be introduced in two equal successive spurts into a relatively small absorbent article.

[0024] The basis weight of the lower acquisition and distribution system is 20 g / m 2 ~80g / m 2 It could be.

[0025] The lower acquisition and distribution system may have a dry opacity of at least 25%.

[0026] The layers of absorbent material may extend longitudinally and laterally across the upper and lower acquisition and distribution systems. [Brief description of the drawings]

[0027] While the specification concludes with claims which particularly set forth and distinctly claim the invention, it is believed that the contents of this specification will be better understood by reference to the following description taken in conjunction with the accompanying drawings, in which: [Figure 1] 1 is an exemplary absorbent article in the form of a diaper. [Figure 2A] 2 is a cross-sectional view of the diaper of FIG. 1 showing a lower acquisition and distribution layer located between and in direct contact with the lower substrate layer and the backsheet. [Figure 2B] 2 is a cross-sectional view of the diaper of FIG. 1 showing a lower acquisition and distribution system located between and in direct contact with the layer of absorbent material and the lower substrate layer. [Figure 2C] FIG. 11 is a cross-sectional view of yet another alternative diaper showing a lower acquisition and distribution layer located between and in direct contact with the layer of absorbent material and the backsheet. [Diagram 3] FIG. 1 is a perspective view of an exemplary device for the NMR MOUSE test method for analyzing fluid distribution in an absorbent article. [Figure 4] FIG. 4 is an alternative perspective view of the exemplary device of FIG. 3 for the NMR MOUSE test method for analyzing fluid distribution in an absorbent article. [Diagram 5] FIG. 4 is an alternative perspective view of the exemplary device of FIG. 3 for the NMR MOUSE testing method for analyzing fluid distribution in an absorbent article when the top plate and bladder assembly of the pressure chamber are separated to allow for sample insertion. [Figure 6] FIG. 4 is yet another alternative perspective view of the exemplary device of FIG. 3 for the NMR MOUSE testing method for analyzing fluid distribution in an absorbent article when the top plate of the pressure chamber and the bladder assembly are separated and a bladder and sample are placed therein. [Figure 7] FIG. 1 is a perspective view of an exemplary deposition assembly for the NMR MOUSE testing method suitable for cooperative engagement with a top plate of an exemplary pressure chamber. [Figure 8] FIG. 1 is a perspective view of an exemplary deposition assembly cooperatively engaging an invasive application opening disposed in a top plate of an exemplary pressure chamber. [Figure 9] FIG. 1 shows an exemplary schematic top view of three profiling spots (x) used in the NMR MOUSE test method. [Figure 10] 1 shows the apparatus used in the modified fluid capture test. [Figure 11A] FIG. 13 is a side view of a curved component used in the modified fluid capture test. [Figure 11B] FIG. 34B is an end view of the curved component of FIG. 34A. [Figure 11C] FIG. 34B is a bottom view of the curved component of FIG. 34A. [Figure 11D]FIG. 34B is a bottom perspective view of the curved component of FIG. 34A. [Figure 11E] FIG. 35 is a top perspective view of the curved component of FIG. 34. [Figure 12A] 1 shows the top plate assembly used in the modified fluid capture test. [Figure 12B] 1 shows the equipment used in the modified fluid capture test. [Figure 13] FIG. 1 is a schematic diagram of a vented bonder. [Figure 14] 1 is a package of an absorbent article of the present disclosure, the article being partially cut away to show the package. [Figure 15] 1 shows a schematic setup for performing horizontal bend drop tests. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0028] Definition of Terms As used herein, "absorbent article" refers to a device that absorbs and contains bodily exudates, and more specifically, refers to a device that is placed against or proximal to the wearer's body to absorb and contain various exudates discharged from the body. Absorbent articles include diapers (baby and toddler diapers and adult incontinence diapers), pants (baby, toddler and adult), absorbent inserts (intended to be inserted into an outer cover to form a diaper or pants), feminine care absorbent articles such as sanitary napkins and panty liners, and the like. As used herein, the term "exudates" includes, but is not limited to, urine, blood, vaginal discharge, sweat, and feces. Preferred absorbent articles of the present invention are disposable absorbent articles, more preferably disposable diapers and disposable pants.

[0029] As used herein, "diaper" and "pants" refer generally to absorbent articles worn by infants, toddlers and incontinent adults around the lower torso to encircle the waist and legs of the wearer, and specifically adapted to receive and contain urinary and fecal exudates. In a pant, as used herein, the longitudinal edges of a first waist region and a second waist region are attached to one another to preform waist and leg openings. The pant is placed in position on the wearer by inserting the wearer's legs into the leg openings and sliding the pant absorbent article into position about the wearer's lower torso. The pant may be preformed by any suitable technique, including but not limited to, joining portions of the absorbent article together using reattachable and / or non-reattachable attachments (e.g., stitching, welding, adhesives, cohesive attachments, fasteners, etc.). The pant may be preformed at any location along the circumference of the article (e.g., side fastening, front waist fastening). In a diaper, the waist opening and leg openings are only formed when the diaper is applied to a wearer by (releasably) attaching the longitudinal edges of the first and second waist regions to one another on both sides by a suitable fastening system.

[0030] As used herein, "panty liners" and "sanitary napkins" generally have two end regions and a middle region (i.e., a crotch region). Panty liners and sanitary napkins have a body-facing surface and a garment-facing surface. The size and shape of the absorbent structure located between the topsheet and the backsheet can be modified to meet absorbent capacity requirements and provide comfort to the wearer. The garment-facing surface of panty liners and sanitary napkins can have a pressure-sensitive adhesive thereon for adhering to the wearer's undergarments. Typically, such adhesive is covered with a release strip that is removed before adhering to the undergarments. Panty liners may also comprise lateral extensions, commonly known in the art as "flaps" or "wings", that are typically intended to extend over and cover the panty elastics in the crotch region of the user's undergarments. However, wings are not typically used with panty liners, but are more often used in sanitary napkins. The sanitary napkins and panty liners of the present invention include barrier leg cuffs.

[0031] As used herein, "disposable" is used in its ordinary sense to mean an article that is disposed of or discarded after a limited number of uses over various periods of time, for example, less than 20 uses, less than 10 uses, less than 5 uses, or less than 2 uses. When the disposable absorbent article is a diaper, pants, sanitary napkin, sanitary pad, or wipes for personal hygiene use, the disposable absorbent article is most often intended to be disposed of after only one use.

[0032] The term "layer of absorbent material" as used herein refers to a component that is disposed or intended to be disposed in an absorbent article between the topsheet and the backsheet. The layer of absorbent material may be surrounded by a core wrap. The core wrap may be formed of an upper substrate layer, such as a nonwoven web, and a lower substrate layer, such as a nonwoven web. The lower substrate layer may be formed from or by a layer of a lower ADS. The layer of absorbent material may be cellulose fibers (so-called "airfelt" or "fluff pulp"), synthetic absorbent fibers, superabsorbent materials, or combinations thereof. The layer of absorbent material may be a mixture of cellulose fibers and superabsorbent materials. The layer of absorbent material may also include a small amount of adhesive (e.g., less than 2.0% by weight, or less than 1.5% by weight, or less than 1.0% by weight of adhesive, based on the total weight of the layer of absorbent material). The layer of absorbent material of the present invention comprises a superabsorbent material, which may constitute at least 30% by weight, or at least 40% by weight, or at least 50% by weight, or at least 60% by weight, or at least 70% by weight, or at least 80% by weight, or at least 90% by weight, based on the total weight of the layer of absorbent material. The superabsorbent material may be in the form of superabsorbent polymer fibers, superabsorbent polymer foams, or preferably superabsorbent polymer particles.

[0033] As used herein, the terms "nonwoven web" and "nonwoven layer" are used interchangeably. They refer to materials that are manufactured webs / layers of directional or randomly oriented fibers. The fibers may be of natural origin or manmade. The natural fibers may be selected from the group consisting of wheat straw fibers, rice straw fibers, flax fibers, bamboo fibers, cotton fibers, jute fibers, hemp fibers, sisal fibers, bagasse fibers, hesper aloe fibers, thatch, saltwater or freshwater algae / seaweed, silk fibers, and combinations thereof. Preferably, the natural fibers are selected from the group consisting of cotton fibers, bamboo fibers, or mixtures thereof. Preferably, the natural fibers are cotton fibers. The synthetic fibers may be selected from the group consisting of polyolefins (such as polyethylene, polypropylene, or combinations and mixtures thereof), polyethylene terephthalate (PET), co-PET, polylactic acid (PLA), polyhydroxyalkaloids (PHA), or mixtures or combinations thereof.

[0034] The fibers in a nonwoven web are consolidated by friction and / or cohesion and / or adhesion, except for paper and woven, knitted, tufted, stitchbonded products. The fibers can be staple fibers (e.g., carded nonwoven webs / layers) or continuous fibers (e.g., spunbond or meltblown nonwoven webs / layers).

[0035] Nonwoven webs / layers can be formed by many processes, such as meltblowing, spunlay, solvent spinning, electrospinning and carding, and the fibers can be consolidated, for example, by hydroentanglement (in spunlaced nonwoven webs / layers), air-through bonding (using hot air blown through the fiber layer in the thickness direction), needle punching, one or more bond patterns and bond impressions created by localized compression and / or application of heat or ultrasonic energy, or combinations thereof. The fibers can alternatively or additionally be consolidated by the use of a binder. The binder can be provided in the form of binder fibers (which are then melted) or in a liquid, such as a styrene butadiene binder. The liquid binder is provided to the fibers (e.g., by spraying, printing or foam application) and then cured to solidify.

[0036] The basis weight of nonwoven fabrics is usually measured in grams per square meter (g / m 2 )

[0037] "Monocomponent" refers to fibers formed of a single polymeric component or a single blend of polymeric components, as distinguished from bicomponent or multicomponent fibers.

[0038] "Bicomponent" refers to a fiber having a cross-section that includes two separate polymeric components, two separate blends of polymeric components, or one separate polymeric component and a blend of one separate polymeric component. "Bicomponent fiber" is subsumed within the term "multicomponent fiber." Bicomponent fibers can have an overall cross-section that is divided into subsections of two different components in any shape or arrangement, including, for example, concentric core and sheath subsections, eccentric core and sheath subsections, side-by-side subsections, radial subsections, and the like.

[0039] "Multicomponent fibers" include, but are not limited to, "bicomponent fibers." Multicomponent fibers may have an overall cross-section divided into different component subsections of any shape or arrangement, including, for example, concentric core and sheath subsections, eccentric core and sheath subsections, side-by-side subsections, islands-in-the-sea subsections, segmented pie subsections, etc.

[0040] "dtex" as used herein refers to the unit used to indicate the fineness of a filament / fiber. This unit represents the mass of the filament / fiber in grams per 10,000 meters of length.

[0041] The terms "mechanically deformed" and "mechanical deformation" as used herein mean that one or more nonwoven webs are mechanically deformed between a first roll and a second roll. If two or more nonwoven webs are overlapped with each other before mechanically deforming them, the webs are intimately combined at the same time as being mechanically deformed. Mechanical deformation depends on the process, the required equipment, and the properties of the substrate, namely, the apparent elongation of the fibers, fiber mobility, the ability to deform and stretch in the area where the mechanical deformation is formed, the ability to undergo plastic deformation, which is hardened after exiting the first and second rolls or partially rebound by elastic recovery.

[0042] The mechanical deformation may include engaging a single nonwoven web or two or more nonwoven webs between a first forming member and a second forming member, so as to obtain a plurality of deformations including three-dimensional protrusions. The mechanical deformation may also introduce openings in the nonwoven, so as to obtain a three-dimensional apertured nonwoven web. Known processes for mechanically deforming nonwoven webs are "selfing" and "ring rolling". They are described, for example, in WO 2016 / 040090 A1.

[0043] As used herein, mechanical deformation does not include embossing of the nonwoven web (although the nonwoven web may be embossed in addition to being mechanically deformed).

[0044] "Hydrophilic" describes the surface of a substrate that can be wetted by aqueous fluids (e.g., aqueous body fluids) deposited on these substrates. Hydrophilicity and wettability are typically defined by the contact angle of the fluid and the breakthrough time of the fluid, e.g., through a nonwoven fabric. This is described in detail in a publication of the American Chemical Society, edited by Robert F. Gould, entitled "Contact Angle, Wettability and Adhesion", Copyright 1964. The surface of a substrate is said to be wetted by a fluid (i.e., hydrophilic) either when the contact angle between the fluid and the surface is less than 90° or when the fluid tends to spread spontaneously across the surface of the substrate (usually both conditions coexist). Conversely, if the contact angle is greater than 90° and the fluid does not spread spontaneously across the surface of the fiber, the substrate is considered "hydrophobic".

[0045] "Longitudinal" refers to a direction extending substantially perpendicular from a waist edge to an opposing waist edge of the article and generally parallel to the maximum linear dimension of the article. "Transverse" refers to a direction perpendicular to the longitudinal direction.

[0046] "Inner" and "outer" refer to the relative location of an element, or a surface of an element, or a group of elements, respectively. "Inner" means that the element or surface is closer to the wearer's body during wear than any other element or surface. "Outer" means that the element or surface is farther away from the wearer's body during wear (i.e., closer to the wearer's garment that may be worn over the article) than any other element or surface.

[0047] "Body-facing" and "garment-facing" refer to the relative position of an element, or a surface of an element, or a group of elements, respectively. "Body-facing" means that an element or surface is closer to the wearer during wear than another element of the same component. An example is an inner layer of an elastic laminate of the present invention, where the inner layer (which is an element of the elastic laminate) is closer to the wearer's body than an outer layer (which is another element of the elastic laminate). "Garment-facing" means that an element or surface is farther away from the wearer during wear than another element of the same component. A garment-facing surface may face another (i.e., other than the wearable article) garment of the wearer, other articles such as bedding, or the atmosphere.

[0048] "Comprise, comprise, and comprising" are open-ended terms, each of which specifies the presence of the subsequently described feature (e.g., component) but does not exclude the presence of other features (e.g., elements, steps, components known in the art or disclosed herein). These terms based on the verb "comprise" encompass the narrower term "consisting essentially of," which excludes any unmentioned element, step, or ingredient that materially affects the manner in which the feature performs its function, and the term "consisting of," which excludes any unspecified element, step, or ingredient.

[0049] 1 is a plan view of an exemplary diaper 20 shown laid out flat with portions of the structure cut away to more clearly show the structure of the diaper 20. As noted above, the diaper 20 is shown for illustrative purposes only, as the structure of the present invention may be configured as a wide variety of diapers or other absorbent articles, such as pants.

[0050] As shown in Figure 1, an absorbent article, here a diaper, may include a topsheet 24, a backsheet 26, and a layer of absorbent material 28 positioned between the topsheet 24 and the backsheet 26. The layer of absorbent material 28 is capable of absorbing and containing liquid received by the absorbent article. Absorbent articles of the present invention, such as the diaper 20 shown in Figure 1, include a lower acquisition and distribution system and may also include an upper acquisition and distribution system (ADS) 50. The upper ADS may include an upper 52 and a lower 54 layer.

[0051] The absorbent article may also include barrier leg cuffs 34, and may further include elastic leg cuffs 32. Additionally, the absorbent article may further include a fastening system, such as an adhesive fastener system or a surface fastener member, which may include a tape tab 42, such as an adhesive tape tab, or a tape tab including a hook element, that cooperates with a landing area 44 (e.g., a nonwoven web that provides a loop in the surface fastener system).

[0052] A diaper or pant, such as the diaper 20 shown in Figure 1, can be conceptually divided into a first waist region 36 (which may be a front waist region), a second waist region 38 (which may be a back waist region) opposite the first waist region 36, and a crotch region 37 located between the first waist region 36 and the second waist region 38. A longitudinal centerline 80 is an imaginary line that divides the diaper in half along its length. A transverse centerline 90 is an imaginary line that is perpendicular to the longitudinal line 80 in the plane of a fully flattened diaper and runs through the middle of the length of the diaper (the same is true for the transverse centerlines and longitudinal lines of other absorbent articles of the present invention). The periphery of the diaper 20 is defined by the outer edges of the diaper 20. The longitudinal edges 13 of the diaper may extend generally parallel to a longitudinal centerline 80 of the diaper 20, and the end edges (front waist edge 10 and back waist edge 12) extend between the longitudinal edges generally parallel to a transverse centerline 90 of the diaper 20. The crotch region, first waist region and second waist region each comprise one-third of the absorbent article along the longitudinal centerline.

[0053] Additionally, the absorbent article may include other elements such as back waist features, which may be inelastic or elastic, and front waist features, which may be inelastic or elastic, lotion, which may be applied on the body-facing surface of the topsheet, back ears 40 and / or front ears 46.

[0054] Alternatively, the front and / or back ears 40, 46 may be separate components attached to the absorbent article, or instead may be continuous with portions of the topsheet and / or backsheet such that they form all or a portion of the front and / or back ears 40, 46. Combinations of the above are also possible, whereby the front and / or back ears 40, 46 are formed by portions of the topsheet and / or backsheet, while additional material is applied to form the entire front and / or back ears 40, 46. The front and / or back ears may be elastic or inelastic. Also, the front ears 40 may be applied as separate components attached to the absorbent article, while the back ears (or portions thereof) 46 may be continuous with portions of the backsheet and / or topsheet, or vice versa.

[0055] The topsheet 24, backsheet 26 and layer of absorbent material 28 may be assembled in a variety of well-known configurations, such as by gluing, heat embossing, ultrasonic bonding or combinations thereof. Exemplary diaper constructions are outlined in U.S. Patent Nos. 3,860,003, 5,221,274, 5,554,145, 5,569,234, 5,580,411 and 6,004,306.

[0056] The topsheet 24 is the portion of the absorbent article 10 that is in direct contact with the wearer's skin. The topsheet 24 may be joined to portions of the backsheet 26, the layer of absorbent material 28, the upper nonwoven core web that covers the layer of absorbent material toward the topsheet, the barrier leg cuffs 32, and / or any other layers known to those skilled in the art. The topsheet 24 may be conformable, soft feeling, and non-irritating to the wearer's skin. Additionally, at least a portion of the topsheet, or the entire topsheet, may be liquid permeable, allowing liquid body exudates to readily penetrate through its thickness. Suitable topsheets may be manufactured from a wide range of materials, such as, for example, porous foams, reticulated foams, perforated plastic films, woven materials, nonwoven materials, woven or nonwoven materials of natural fibers (e.g., wood fibers or cotton fibers), synthetic fibers or filaments (e.g., polypropylene fibers, or bicomponent PE / PP fibers, or mixtures thereof), or combinations of natural and synthetic fibers. The topsheet may have one or more layers. The topsheet may be perforated or non-perforated, may have any suitable three-dimensional features, and / or may have a plurality of embossments (e.g., bond patterns). Any portion of the topsheet may be coated with a skin care composition, an antimicrobial agent, a surfactant, and / or other benefit agent. The topsheet may be hydrophilic or hydrophobic, or may have hydrophilic portions or layers and / or hydrophobic portions or layers. If the topsheet is hydrophobic, there will typically be holes to allow bodily exudates to pass through the topsheet.

[0057] The backsheet 26 is that portion of the absorbent article 20 that generally constitutes all or a portion of the garment-facing surface of the absorbent article. The backsheet 26 may be joined to portions of the topsheet 24, the layer of absorbent material 28, the lower nonwoven core web, the lower acquisition and distribution system (or a layer of the lower ADS that is in direct contact with the backsheet and / or any other layer of the absorbent article by any attachment method known to those skilled in the art). The backsheet 26 prevents, or at least inhibits, bodily exudates absorbed and contained in the layer of absorbent material 28 from soiling articles such as bed sheets, undergarments, and / or clothing. The backsheet is typically liquid impermeable, or at least substantially liquid impermeable.

[0058] The backsheet may be or include a thin plastic film 39, such as a thermoplastic film having a thickness of from about 0.012 mm to about 0.051 mm. Other suitable backsheet materials may include breathable materials that allow vapors to escape from the absorbent article while still preventing, or at least inhibiting, body exudates from passing through the backsheet.

[0059] The backsheet may be breathable. The breathable backsheet has a modulus of elasticity between 1,000 and 15,000 g / m2, as measured using a PERMATRAN-W Model 101K (Mocon, Inc., Minneapolis, MN) or equivalent in accordance with Nonwoven Standard Procedure NWSP 70.4.R 0(15), with the following specifications: experiments are conducted in a controlled laboratory at 23°C ± 2°C and 50% RH ± 2% RH, and the instrument cell is heated to 37.8°C (100°F). 2 / h, or 1,000 to 10,000 g / m 2 / h, or 1,500 to 10,000 g / m 2 / h water vapor transmission rate (WVTR).

[0060] The backsheet 26 may include a backsheet outer cover nonwoven web 40. The backsheet outer cover nonwoven web may include one or more nonwoven materials joined to and covering the backsheet film 39. The outer cover nonwoven web 40 may form the garment-facing surface of the backsheet, such that a film may not be present on the garment-facing surface. The backsheet outer cover nonwoven material 40 may include bond patterns, openings, and / or three-dimensional features.

[0061] The absorbent article 20 may have a length greater than 450 mm or less than 450 mm. The length of the absorbent article is determined when all elastic strands (such as leg elastics) that prevent the flattened configuration are cut and thus de-elasticated, and the absorbent article is laid flat. The length is determined along the longitudinal centerline.

[0062] The layer of absorbent material 28 comprises superabsorbent polymer particles and, optionally, cellulose fibers. The layer of absorbent material may be supported by one or more substrate layers. An upper substrate layer 45 may be provided between the upper ADS 50 and the layer of absorbent material 28. If the absorbent article does not include an upper ADS, an upper substrate layer may be provided between the topsheet and the layer of absorbent material. A lower substrate layer 46 may be provided between the layer of absorbent material 28 and the lower ADS. Instead of the lower substrate layer 46, the lower ADS 60 may be in direct contact with the layer of absorbent material 28 (i.e., there is no lower substrate layer 46).

[0063] The upper substrate layer 45 and the lower substrate layer 46 may partially or completely surround the layer of absorbent material 28. Alternatively, the upper substrate layer 45 and the lower ADS 60 may partially or completely surround the layer of absorbent material 28.

[0064] The layer of absorbent material 28 may be partially or completely surrounded by an upper substrate layer 45 and a lower substrate layer 46, the upper substrate layer 45 may be between the layer of absorbent material 28 and the upper acquisition and distribution system 50, and the lower substrate layer 46 may be between the layer of absorbent material 28 and the lower acquisition and distribution system 60. Such an embodiment is exemplarily shown in FIG. 2A. In such an embodiment, a) the lower acquisition and distribution system 60 may be hydrophobic and the lower substrate layer 46 may be hydrophilic, or b) the lower acquisition and distribution system 60 and the lower substrate layer 46 may both be hydrophilic, with the lower acquisition and distribution system 60 being less hydrophilic than the lower substrate layer 46, or c) the lower acquisition and distribution system 60 and the lower substrate layer 46 may both be hydrophobic and the lower substrate layer 46 being less hydrophobic than the lower acquisition and distribution system 60.

[0065] Alternatively, the layer of absorbent material 28 and the lower acquisition and distribution system 60 may be partially or completely surrounded by and in direct contact with the upper and lower substrate layers 45 and 46, where the upper substrate layer 45 may be between the layer of absorbent material 28 and the upper acquisition and distribution system 50, and the lower substrate layer 46 may be between the lower acquisition and distribution system 60 and the backsheet, with the layer of absorbent material 28 in direct contact with the lower acquisition and distribution system 60. An embodiment of such a configuration is illustrated in Figure 2C.

[0066] In yet another alternative, the layer of absorbent material 28 may be partially or completely surrounded by the upper substrate layer 45 and the lower acquisition and distribution system 60, and the upper substrate layer 45 may be between the layer of absorbent material 28 and the upper acquisition and distribution system 50. Such an embodiment is illustratively shown in Figure 2B.

[0067] The upper and lower substrate layers may be made of the same material, i.e., the same nonwoven web, or they may be made of different materials, i.e., two different nonwoven webs. The upper and lower substrate layers may also be made of a single continuous material, such as a single continuous nonwoven web wrapped around a layer of absorbent material, for example in a c-wrap configuration.

[0068] The portions of the upper substrate layer 45 at and adjacent to the longitudinal edges may be folded over the longitudinal edges of the absorbent layer such that these portions are positioned on the garment-facing surface of the absorbent layer. Alternatively or additionally, the portions of the lower substrate layer 46 at and adjacent to the longitudinal edges may be folded over the longitudinal edges of the absorbent layer such that these portions are positioned on the body-facing surface of the absorbent layer. The absorbent layer may be secured onto the upper substrate layer 45 and / or the lower substrate layer 46 and / or onto the lower ADS 60, for example by using a hot melt adhesive.

[0069] The upper and lower substrate layers 45, 46 can be any material capable of supporting a layer of absorbent material. The substrate layers can be web or sheet materials such as foams, films, woven fabrics, or preferably nonwoven webs. The upper and lower substrate layers 45, 46 can be separate and distinct sheets of material (such as two nonwoven webs) or can be formed from a continuous sheet (such as a continuous nonwoven web) wrapped around the layer of absorbent material.

[0070] The layer of absorbent material 28 includes a superabsorbent polymer, such as superabsorbent polymer particles, and may optionally include cellulose fibers.

[0071] The layer absorbent material may comprise at least 30% by weight, or at least 40% by weight, or at least 50% by weight, or at least 60% by weight, or at least 70% by weight, or at least 80% by weight, or at least 90% by weight of superabsorbent polymer particles, based on the total weight of the absorbent layer. The layer of absorbent material may comprise less than 25% by weight, or less than 20% by weight, or less than 15% by weight, or less than 10% by weight, or less than 5% by weight, or even no cellulose, based on the total weight of the layer of absorbent material.

[0072] The superabsorbent polymer particles and cellulose fibers may be homogeneously mixed with each other such that the ratio of cellulose fibers to superabsorbent polymer particles is substantially the same throughout the layer of absorbent material. Alternatively, the superabsorbent polymer particles and cellulose fibers may be heterogeneously mixed such that the ratio of cellulose fibers to superabsorbent polymer particles is higher toward the front and rear edges of the layer of absorbent material compared to the central region of the layer of absorbent material. The region toward the front edge of the layer of absorbent material, the region toward the rear edge of the layer of absorbent material, and the central region may each extend along 1 / 3 of the longitudinal dimension of the absorbent layer along the longitudinal centerline.

[0073] When the layer of absorbent material does not contain cellulose, the only absorbent material in the absorbent layer may be superabsorbent polymer (particles, fibers or foam). The resulting layer of absorbent material has a reduced thickness in the dry state compared to conventional absorbent cores that contain cellulose fibers. The reduced thickness helps improve the fit and comfort of the absorbent article to the wearer.

[0074] The layer of absorbent material may include one or more regions that are free of absorbent material and completely surrounded by absorbent material. These regions may therefore be free of cellulose fibers and superabsorbent polymer particles. The absorbent material-free regions may be elongated regions having a length of 20%-80%, or 20%-70%, or 30%-60% based on the overall longitudinal dimension of the layer of absorbent material. The elongated regions may be straight, curved, or a combination thereof. The layer of absorbent material may have only one absorbent material-free region or may include two or more absorbent material-free regions. The two or more absorbent material-free regions may be configured such that they are symmetrical about the longitudinal centerline of the absorbent article.

[0075] The superabsorbent polymer particles constituted by the layer of absorbent material may be spherical, spherical-like, ellipsoidal, or irregularly shaped, such as ovoid particles of the type that may be obtained from inverse suspension polymerization. The particles may also be optionally aggregated, at least to some extent, to form larger irregular particle agglomerates.

[0076] The superabsorbent polymer particles can be selected from polyacrylates and polyacrylate-based materials that are internally and / or surface crosslinked, such as partially neutralized crosslinked polyacrylates or acid polyacrylates. Examples of absorbent polymer particles suitable for the present disclosure are described, for example, in WO 07 / 047598, WO 07 / 046052, WO 2009 / 155265, and WO 2009 / 155264.

[0077] Due to the presence of the lower ADS, the absorbent article of the present invention has a fast acquisition speed, as reflected by the total acquisition time in the various examples below. The total acquisition time of the absorbent article can be less than 120 seconds, or less than 100 seconds, when measured according to the test methods described herein.

[0078] Upper Acquisition and Distribution System (ADS) The upper ADS 50 may be disposed between the layer of absorbent material 28 and the topsheet 24. The upper ADS may be in direct contact with the layer of absorbent material 28 and the topsheet 24. If the absorbent article includes an upper substrate layer that at least partially surrounds the layer of absorbent material 28, the upper ADS may be in direct contact with the topsheet 24 and upper substrate layer 45.

[0079] The upper ADS acts as a temporary reservoir of liquid until the layer of absorbent material can absorb and store the liquid, and then distribute the liquid to the layer of absorbent material in an efficient manner. The upper ADS may consist of a single layer or may include multiple layers, such as an upper layer 52 adjacent the topsheet 24 and facing the wearer's body, and a lower layer 54 between the upper layer 52 and the layer of absorbent material, facing the wearer's garment.

[0080] The prior art discloses many types of capture and distribution systems, see for example WO 2000 / 59430, WO 95 / 10996, US Pat. No. 5,700,254, WO 02 / 067809.

[0081] The upper ADS may be free of superabsorbent polymers. The upper ADS may also be free of unmodified cellulose fibers.

[0082] The function of the lower layer 54 of the upper ADS 50 is typically to spread the discharged fluid over a larger surface area in the absorbent article so that the absorption capacity of the layer of absorbent material can be used more efficiently. The lower layer 54 of the upper ADS can be made of a nonwoven web having a relatively low density based on synthetic or cellulosic fibers. The lower layer of the upper ADS typically has a density of 30 to 400 g / m 2 , specifically 80 to 300 g / m 2 The bottom layer of the upper ADS may not be formed from a coherent self-supporting web or sheet, but may be a layer that has little integrity of its own.

[0083] The lower layer of the upper ADS may, for example, comprise at least 50% by weight, or 60% by weight, or 70% by weight, or 80% by weight, or 90% by weight of crosslinked cellulose fibers. The crosslinked cellulose fibers may be crimped, twisted, or curled, or a combination thereof including crimped, twisted, and curled. The crosslinked cellulose fibers provide higher resilience and therefore higher resistance to compression in product packaging or under use conditions of absorbent articles, such as under the weight of a baby, compared to unmodified cellulose fibers. This provides the lower layer of the upper ADS with a relatively high void volume, permeability, and liquid absorbency, which reduces leakage and improves dryness.

[0084] The lower layer of the upper ADS containing crosslinked cellulose fibers may contain other fibers, but this layer may advantageously contain at least 50%, or 60%, or 70%, or 80%, or 90%, or even up to 100% crosslinked cellulose fibers by weight of the layer. An example of such a mixed layer of crosslinked cellulose fibers may contain 70% by weight of chemically crosslinked cellulose fibers, 10% by weight of polyester (PET) fibers, and about 20% by weight of untreated pulp fibers. In another example, the layer of crosslinked cellulose fibers may contain 70% by weight of chemically crosslinked cellulose fibers, 20% by weight of lyocell fibers, and 10% by weight of PET fibers. In another example, the layer may contain 68% by weight of chemically crosslinked cellulose fibers, 16% by weight of untreated pulp fibers, and 16% by weight of PET fibers.

[0085] The upper ADS may further comprise an upper layer 52, which typically functions to quickly capture fluid away from the topsheet to provide good dryness to the wearer. The upper layer of the upper ADS is typically located directly below the topsheet and directly above the lower layer of the upper ADS. The upper layer of the upper ADS may typically be or include an SMS or SMMS material, including, for example, two spunbond (S) outer layers with one or more meltblown (M) layers in between, or alternatively a carded nonwoven web that includes a binder to consolidate the fibers and provide web integrity. The nonwoven web may in particular be one that is bonded by a latex binder. An exemplary upper layer of the upper ADS is disclosed in US Pat. No. 7,786,341. A carded resin-bonded nonwoven web may be used, in particular when the fibers used are solid round or round hollow PET staple fibers (50 / 50 or 40 / 60 mix of 6 denier and 9 denier fibers).

[0086] The top layer of the upper ADS, to which the carded resin is bound, can be stabilized by a latex binder, for example a styrene-butadiene latex binder (SB latex). Processes for obtaining such a lattice-like structure are known, for example, from EP 149 880 (Kwok) and US 2003 / 0105190 (Diehl et al). The binder may be present in the top layer of the upper ADS in an amount of more than 15% or 20% by weight, but not more than 40% or not more than 35% by weight of the top layer. SB latex is available, for example, under the trade name GENFLO™ 3160 (OMNOVA Solutions Inc., Akron, Ohio).

[0087] Lower Acquisition and Distribution System (ADS) The lower ADS 60 may be disposed between the layer of absorbent material 28 and the backsheet 26. The lower ADS may be in direct contact with the layer of absorbent material 28 and the topsheet 26. If the absorbent article includes a lower substrate layer 46 that, together with the upper substrate layer, at least partially surrounds the layer of absorbent material 28, the lower ADS may be in direct contact with the topsheet 24 and the lower substrate layer 45.

[0088] The lower ADS may act as a temporary reservoir for liquid that has not been absorbed rapidly enough by the absorbent material of the layer of absorbent material and has therefore flowed through the layer of absorbent material.

[0089] Additional layers provided in absorbent articles generally increase the thickness and bulk of the article, which may lead to increased bending stiffness and therefore shortcomings in terms of the conformity and close contact of the article to the wearer's body, thereby reducing the comfort of the wearer. Also, increased bulk, especially between the wearer's legs, is generally undesirable. Therefore, the thickness and bulk of the lower ADS should be carefully selected.

[0090] In order not to unduly increase the stiffness of the absorbent article, the lower ADS may have a horizontal bend drop according to the test method described below of greater than 60, preferably greater than 70. A higher value of horizontal bend drop indicates a softer material relative to a lower value.

[0091] On the other hand, the lower ADS is preferably a relatively thick material (such as a spunlace or air-through bonded nonwoven web) that provides sufficient void volume to be able to capture and retain fluids that penetrate the layer of absorbent material. It has been found that the lower ADS can have a lower basis weight and lower thickness than the upper ADS because the amount of fluids that can potentially penetrate the layer of absorbent material is generally lower than the amount of liquid that needs to be handled by the upper ADS. Also, the lower ADS can consist of only a single material, such as a single layer of material.

[0092] The basis weight of the lower ADS may be uniform throughout the length and width of the lower ADS (i.e., longitudinally and laterally). Such uniform basis weight should not take into account any localized basis weight variations on a somewhat small scale (such as within 1.0 cm, or within 0.5 cm in the width and length directions) that may result from mechanical deformation of the lower ADS.

[0093] The lower ADS may have a smaller longitudinal and / or lateral extension than the layer of absorbent material, such that the layer of absorbent material extends longitudinally and / or laterally beyond the lower ADS. The layer of absorbent material may also extend longitudinally and / or laterally beyond the upper ADS.

[0094] Alternatively, the lower ADS may have a greater longitudinal and / or lateral extension than the layer of absorbent material, such that it extends longitudinally and / or laterally beyond the layer of absorbent material. This may be desirable when the layer of absorbent material is in direct contact with the lower ADS (i.e., there is no lower substrate layer between the layer of absorbent material and the lower ADS). In such a configuration, the layer of absorbent material may be deposited and formed partially or completely on the lower ADS. The layer of absorbent material may be formed partially on the lower ADS and partially on the upper substrate layer, and then both subcomponents of the layer of absorbent material may be combined to form the layer of absorbent material by placing the two subcomponents in interfacing relationship.

[0095] The lower ADS may not include a superabsorbent polymer. The lower ADS may include or consist of a nonwoven web. It may be a spunbond or meltblown nonwoven web (made of continuous fibers) or a carded nonwoven web (made of staple fibers) or a nonwoven with spunbond and meltblown layers (e.g., SMS, SMMS, SMSS, etc.). The nonwoven web may be made of synthetic fibers such as polyolefins (e.g., polyethylene, polypropylene, or mixtures or combinations thereof), polyethylene terephthalate (PET), co-PET, polylactic acid (PLA), polyhydroxyalkanoid (PHA), or combinations or mixtures thereof. The fibers may be continuous or spunbond fibers.

[0096] The fibers can be monocomponent fibers or multicomponent fibers, such as bicomponent fibers. When the fibers included in the lower ADS are bicomponent fibers, they have a core-sheath configuration, with the core component having a higher melting point than the sheath component.

[0097] Preferably, the lower ADS comprises or consists of a nonwoven web that is air-through bonded or spunlaced. Such nonwoven webs generally have a large thickness. Thus, they have a porous structure to provide void volume for absorbing and temporarily retaining liquid. At the same time, they provide softness and do not have excessively high bending stiffness (this is reflected in the horizontal bending drop according to the test method described below).

[0098] The fibers may be continuous, such as in a spunlaid nonwoven web. The spunlaid nonwoven web is preferably air-through bonded or spunlaced. In addition to hydroentanglement (spunlace) or air-through bonding, the spunlaid nonwoven web may be subjected to heat and / or pressure (e.g., point bonding) and some localized bonding to introduce localized bond areas where the fibers are fused together.

[0099] Preferably, however, the fibers included in the lower ADS are staple fibers. As with nonwoven webs made with continuous fibers, the staple fiber nonwoven webs are preferably air-through bonded or spunlaced. In addition to hydroentanglement (spunlace) or air-through bonding, the staple fiber nonwoven webs may be subjected to heat and / or pressure (e.g., point bonding) and some localized bonding to introduce localized bond areas where the fibers are fused together.

[0100] Regardless of whether the nonwoven web is made of continuous or staple fibers, the localized bonds, however, must not adhere to too large a surface area and thus adversely affect the thickness and void volume of the nonwoven web. Preferably, the total bond area provided by localized heat and / or pressure bonds (in addition to hydroentanglement or air-through bonding) should not be greater than 20%, or greater than 15%, or greater than 10% of the total surface area of ​​the nonwoven web.

[0101] Alternatively, the nonwoven web included in the lower ADS should not be subjected to any bonding and consolidation in addition to hydroentanglement (spunlace) or air-through bonding, so that the advantageous properties of such nonwoven webs can be optimally utilized.

[0102] In spunlaced nonwoven webs, the fibers are subjected to hydroentanglement to intermingle and intertwine with each other. The consolidation and entanglement of the fibers with each other can be obtained by multiple water jets under pressure that pass through a moving fleece or fabric and cause the fibers to interweave with each other like needles. Thus, the consolidation of the spunlaced nonwoven web is essentially the result of hydroentanglement. As used herein, "spunlaced nonwoven web" also refers to a nonwoven fabric formed from two or more precursor webs that are combined with each other by hydroentanglement. The two or more webs may be subjected to a bonding process, such as heat and / or pressure bonding, for example by applying a bonding pattern using a patterned calendar roll and anvil roll, before being combined into one nonwoven fabric by hydroentanglement. However, the two or more webs are combined with each other only by hydroentanglement. Alternatively, the spunlaced nonwoven web is a single web, i.e., it is not formed of two or more precursor webs. The spunlaced nonwoven layer / web can be made of staple fibers or continuous fibers.

[0103] Through air bonding (used interchangeably with the term "air through bonding") refers to the process of bonding staple or continuous fibers by forcing air through the nonwoven web, where the air is hot enough to melt (or at least partially melt, or melt until the surface of the fiber is sufficiently tacky) the polymer of the fiber, or, if the fiber is a multicomponent fiber, the air is hot enough to melt (or at least partially melt, or melt until the surface of the fiber is sufficiently tacky) one of the polymers from which the fibers of the nonwoven web are made. Air speeds are typically 30 to 90 meters per minute, and residence times can be up to 6 seconds. The melting and resolidification of the polymer provides the bond between the different fibers.

[0104] A through-air bonder is shown diagrammatically in Figure 13. In a through-air bonder 70, air at a temperature higher than the melting temperature of the polymer of the staple or continuous fibers, or higher than the melting temperature of a first fiber component and lower than the melting temperature of a second fiber component if the staple or continuous fibers are multicomponent fibers, is directed from a hood 72 through the web and into a perforated roller 74. Alternatively, the through-air bonder can be a flat arrangement where air is directed vertically downward onto the web. The operating conditions of the two configurations are similar, the main difference being the geometry of the web being bonded.

[0105] The hot air melts the staple or continuous fibers, or, in the case of multicomponent fibers, the lower melting polymer component of the fibers, thereby forming bonds between the staple fibers and consolidating and consolidating the layers of staple fibers into a web.

[0106] The nonwoven layer included in or forming the lower ADS may comprise multicomponent fibers. The fibers of the nonwoven included in the lower acquisition and distribution layer may comprise at least 30% by weight, or at least 40% by weight, or at least 50% by weight, or at least 70% by weight, or at least 90% by weight, or 100% by weight of multicomponent fibers, based on the total weight of the nonwoven included in the lower acquisition and distribution layer. The multicomponent fibers may be bicomponent fibers, such as core-sheath or side-by-side bicomponent fibers.

[0107] Alternatively, the nonwoven layer included in or forming the lower ADS may comprise monocomponent fibers. The fibers of the nonwoven included in the lower acquisition and distribution layer may comprise at least 30% by weight, or at least 40% by weight, or at least 50% by weight, or at least 70% by weight, or at least 90% by weight, or 100% by weight of monocomponent fibers, based on the total weight of the nonwoven included in the lower acquisition and distribution layer. The nonwoven web included in or forming the lower ADS may comprise a mixture of monocomponent and multicomponent fibers.

[0108] The nonwoven layer of the lower ADS is preferably of very thick construction, so the use of crimped fibers may be beneficial. Such fibers also provide a nonwoven layer with good recovery, i.e., the nonwoven web has the ability to recover its original caliper (or almost its original caliper) after being compressed for a long time (e.g., while being contained in a closed package containing a highly compressed absorbent article). The crimped fibers may have a flat crimp (so-called 2-dimensional crimp) or a 3-dimensional crimp, such as a spiral crimp. Bicomponent fibers are well known to be suitable for obtaining crimped fibers.

[0109] The fibers of the nonwoven fabric included in the lower acquisition and distribution layer may comprise at least 30% by weight, or at least 40% by weight, or at least 50% by weight, or at least 70% by weight, or at least 90% by weight, or 100% by weight of crimped fibers, based on the total weight of the nonwoven fabric included in the lower acquisition and distribution layer. The crimped fibers may be bicomponent fibers.

[0110] The caliper of the lower acquisition and distribution system is desirably in a range that balances good liquid absorption and retention properties (i.e., sufficient void volume within the nonwoven web) with the need to avoid the lower ADS adding excessive bulk to the absorbent article and thus reducing wearer comfort. The caliper of the lower ADS can be 0.1 to 2.0 mm, or 0.2 to 1.0 mm, as measured according to the test methods described herein below.

[0111] Also, for the lower ADS material, it is desirable to show good recovery after compression, considering that absorbent articles are often packed under relatively high compression. First, a material with suitable characteristics for use as the lower ADS, such as sufficient thickness and void volume, may lose many of these beneficial properties when compressed in a package if it has insufficient ability to recover. This ability is reflected in the Z-compliance index and percent recovery measurement methods described below. Materials suitable as the lower ADS may have a compliance index greater than 4, preferably greater than 10, and a percent recovery greater than 50, preferably greater than 60.

[0112] The basis weight of the lower ADS is 20g / m 2 ~100g / m 2 , or 20 g / m 2 ~80g / m 2 , or 20 g / m 2 ~60g / m 2 It could be.

[0113] The nonwoven included in or forming the lower ADS may be subjected to mechanical deformation, which may contribute to the thickness and openness of the nonwoven web, thus improving the properties of the nonwoven web that are desirable for use as a lower ADS.

[0114] When the wearer- and / or garment-facing surface of the lower ADS has a three-dimensional surface topography (e.g., as obtained by mechanical deformation), so-called "air pockets" may be obtained, especially when the lower ADS is in direct contact with a layer (such as the backsheet or lower substrate layer 46) that has a flat two-dimensional surface topography. The three-dimensional surface of the lower ADS may only contact the adjacent layer (such as the backsheet or lower substrate layer 46) in outwardly protruding areas, leaving small gaps in recessed areas. These gaps may increase the comfort and soft feel of the absorbent article to the wearer.

[0115] It is also desirable to have good air permeability of the lower ADS. Since adding a lower ADS means adding an additional layer of material to the absorbent article, such additional layer should not unduly affect the overall air permeability of the absorbent article. Suitable air permeability of the lower ADS can be obtained by using a porous and relatively open structure of the nonwoven web of the lower ADS, such as a spunlace or air-through bonded nonwoven.

[0116] The lower acquisition and distribution system 60 has a 150m 3 / m 2 / min or 200m 3 / m 2 / min~800m 3 / m 2 / min.

[0117] The dry opacity of the lower acquisition system (i.e., the opacity measured at the dry lower ADS) may be relatively high and contribute to the overall opaque appearance of the absorbent article. Also, having a lower ADS with relatively high opacity may prevent stains (e.g., from urine or feces) in the layer of absorbent material from being visible when viewing the backsheet of the absorbent article during use. The dry opacity of the lower ADS may be at least 25%, or at least 40%, or at least 50%, or at least 70%, as measured according to the Opacity Test Method described below.

[0118] Bio-sourced materials The components of the disposable absorbent articles of the present invention (i.e., diapers, pants, sanitary napkins, panty liners, etc.) may be any of the compositions and methods described in U.S. Patent Application Publication Nos. 2007 / 0219521(A1) published on September 20, 2007 to Hird et al., 2011 / 0139658(A1) published on June 16, 2011 to Hird et al., and 2011 / 0139658(A1) published on June 16, 2011 to Hird et al. No. 0139657(A1), Hird et al., published June 23, 2011, No. 2011 / 0152812(A1), Hird et al., published June 16, 2011, No. 2011 / 0139662(A1), Hird et al., published June 16, 2011, and No. 2011 / 0139659(A1), Hird et al., published June 16, 2011. These components include, but are not limited to, the topsheet nonwoven, the backsheet film, the backsheet nonwoven, the barrier leg cuff nonwoven, the superabsorbent material, the upper and lower substrate layers, the adhesive, the fastener hook, and the fastener landing area nonwoven, and the film base. For example, the upper and / or lower acquisition and distribution layers of the present invention may at least partially comprise biosourced inclusions.

[0119] Components of disposable absorbent articles may comprise a biobased content value of from about 10% to about 100% using ASTM D6866-10, Method B, in other embodiments from about 25% to about 75%, and in yet other embodiments from about 50% to about 60% using ASTM D6866-10, Method B.

[0120] To apply the ASTM D6866-10 methodology to determine the biobased content of any disposable absorbent article component, a representative sample of the disposable absorbent article component must be obtained for testing. The disposable absorbent article component can then be ground to fine particles of less than about 20 mesh using known grinding methods (e.g., a Wiley® mill) and a representative sample of suitable mass can be removed from the randomly mixed particles.

[0121] Test Method NMR MOUSE Test Method The NMR MOUSE test method is used to quantify the liquid distribution in an absorbent article as a function of depth and after applying a liquid insult to a location of interest within the absorbent article. The article is positioned in an apparatus that applies a constant pressure to the absorbent article, and while this pressure is applied, one or more insults of saline solution are applied to a location of interest within the absorbent article. The apparatus is further positioned with a low-field NMR instrument so that the liquid depth profile of the absorbent article under pressure can be measured. From these liquid depth profiles, depth zones of interest are defined, quantified, and reported. General NMR test methods and apparatus are also described in U.S. Patent Nos. 10,371,652 and 10,365,237.

[0122] A device suitable for measuring the two-dimensional profile of fluid distribution through a multi-layer absorbent article is shown in Figures 3-4. The device 100 comprises a frame 120, a pressure chamber 140 and an NMR MOUSE sensor 160. The NMR-MOUSE (Mobile Universal Surface Explorer) is a portable open NMR sensor with a permanent magnet geometry that generates a highly uniform gradient perpendicular to the scanner surface (shown in Figure 3). The flat active volume of the specimen is excited and detected by a surface rf coil placed above the magnet at a position that defines the maximum penetration depth into the specimen. An exemplary instrument is the Profile NMR-MOUSE model PM10 available from Magritek Inc. (San Diego, CA). The requirements for the NMR-MOUSE to achieve a resolution of 50 μm in the z-direction are a measurement frequency of 14.07 MHz, a maximum measurement depth of 10 mm, a static gradient of 13 T / m, and a linearity of 19 m. m× 19m mThe effective volume (xy dimensions). Before enabling the instrument, perform phase alignment, check the resonant frequency, and check the external noise level according to the manufacturer's instructions. All measurements are performed in a room controlled at 23° C.±2° C. and approximately 50%±2% relative humidity. The pressure chamber 140 is formed from a conformable and pressurizable surface, such as the exemplary bladder assembly 180, and a top plate assembly 200 that includes a deposition assembly 220.

[0123] Bladder assembly 180 is constructed of 12.7 mm fiberglass reinforced epoxy (DIN7735 / HGW2372.4) to provide overall dimensions of 80 cm length by 30 cm width by 5 cm height. A manometer 240 is provided for measurement of pressure within pressure chamber 140. A pressure gauge 260 is provided for regulating the introduction of air into pressure chamber 140 and may be positionably mounted through an access hole cooperatively located on the right side of pressure chamber 140.

[0124] 5 illustrates device 100 illustrating the separable and displaceable nature of top plate assembly 200 relative to bladder assembly 180 and frame 120 of pressure chamber 140. As shown in FIG. 5, top plate assembly 200 is attached to bladder assembly 180 and can be rotated about a longitudinal axis of its attachment to bladder assembly 180 to facilitate user access to areas of the interior portion of pressure chamber 140 disposed between top plate assembly 200 and bladder assembly 180.

[0125] 6, the bladder assembly 180 of the pressure chamber 140 may comprise a bladder 320. The bladder 320 may be cooperatively associated and sealingly engaged with the bladder assembly 180 of the pressure chamber 140 by draping the bladder 320 over the top of the bladder assembly 180 with sufficient slack to provide that the bladder 320 contacts the bottom of the bladder assembly 180 at its center point. The bladder 320 may be provided as a 50 mm by 100 mm silicone film having a thickness of 0.02 inches and a Shore A durometer of 20. An exemplary material suitable for use as the bladder 320 is available as part number 86435K85 from McMaster-Carr, Cleveland, Ohio.

[0126] Preferably, a secondary frame 360 ​​having fitting flanges is attached to the top of bladder 320 and secured to bladder assembly 180 with clamps 380. When bladder 320 is sealably secured to bladder assembly 320, the combined bladder / bladder assembly 320 assembly is preferably leak-tight at a pressure of 0.3 psi.

[0127] The front sample support 400 and the rear sample support 420 can be used to secure the sample 340 or article to be measured by the device 100 relative to the bladder assembly 180. If desired, the sample 340 or article can be attached to the front 400 and rear 420 sample supports by attachment means 440. Such attachment can be provided by the end user as determined by one of skill in the art. The attachment means 440 can be provided as an adhesive tape fastener system, a mechanical "hook" fastener, an adhesive attachment system, combinations thereof, and the like. The front sample support 400 and the rear sample support 420 can be adjusted as may be required along the length (i.e., y-axis) of the secondary frame 360. The adjustment of the front sample support 400 and the rear sample support relative to the secondary frame 360 ​​can be provided as a pin-and-hole system, and the like, as would be understood by one of skill in the art to accommodate absorbent articles of different sizes to properly align the fill point of the absorbent article.

[0128] The top plate assembly 200 may be provided by a suitably sized fiberglass reinforced epoxy (DIN7735 / HGW 2372.4) piece reinforced with a support frame 460 for added rigidity. The portion of the top plate assembly 200 positioned adjacent the sample 34, located on the bladder 320 and adjacent the area in which the NMR sensor 160 operates, is preferably essentially transparent to NMR-MOUSE radiation.

[0129] 7-8, the deposition assembly 220 can be disposed on a surface of the top plate assembly 200. The deposition assembly 220 can facilitate disposing an invasive specimen 340 disposed on a bladder 320 disposed within the pressure chamber 140. The deposition assembly 220 is preferably rotatable about an axis R to facilitate disposing and displacing the deposition assembly into and out of contact engagement with an invasive application opening 500 disposed within the top plate assembly 200. The deposition assembly 220 is disposed so as to be centrally located with respect to the top plate assembly 200 and cooperatively aligned with the invasive application opening 500.

[0130] Those skilled in the art will appreciate that a suitable deposition assembly 220 may be constructed from a material transparent to NMR level RF. The deposition assembly 220 is constructed using PA12-GF as a cylinder and an opening of 1 cm x 2 cm. When the deposition assembly 220 is cooperatively aligned with the invasive application opening 500, the deposition assembly 220 is preferably inserted through the top plate assembly 200, through the invasive application opening 500, such that a contact edge 540 of the deposition assembly 220 is cooperatively aligned with a surface of the top plate assembly 200 that contact-engages with a sample 340 disposed within the pressure chamber 140.

[0131] The unique procedure outlined below can facilitate a) measuring the sample 340 profile from the top and b) measuring the sample 340 profile from the bottom. In other words, the described process can facilitate measuring the liquid distribution within a sample 340 (e.g., an absorbent article) within a very short period of time.

[0132] The sample 340 is conditioned at 23°C ± 2°C and about 50% ± 2% relative humidity for 12 hours prior to testing. The sample 340 (e.g., absorbent article) is prepared by laying the sample 340 flat on a lab bench and identifying the intersection of the longitudinal and lateral centerlines of the sample 340. For samples 340 provided as absorbent articles in the form of pants, any cuffs or waistbands are removed so as not to damage the topsheet or layer of absorbent material, the lower and upper acquisition and distribution system, if present, the backsheet, and the upper and lower substrate layers 45, 46, if present, of the sample 340. The sample 340 or article can be attached to the front 400 and rear 420 sample supports of the secondary frame 360 ​​by attachment means 440. The attachment means 440 can be provided as either an adhesive tape or a mechanical "hook" fastener, with the topsheet or backsheet of the sample 340 facing up (i.e., the absorbent article sample 340 is positioned so that the topsheet or backsheet of the absorbent article is positioned in close proximity to the NMR sensor 160).

[0133] The specimen 340 is placed over the secondary frame 360 ​​such that only the chassis (e.g., the portions of the topsheet and backsheet extending outwardly from the layer of absorbent material) and not the layer of absorbent material of the specimen 340 is over the secondary frame 360. The front 400 and rear 420 specimen supports are attached to the secondary frame 360 ​​such that when the top plate assembly 200 is closed over the bladder assembly 180, the absorbent article is centered longitudinally and laterally over the invasive application opening 500. The rear end of the specimen 340 is secured to the rear 420 specimen support of the secondary frame 360 ​​by either adhesive tape or mechanical "hook" fasteners, again such that only the chassis and not the absorbent core is over the application opening 500. The rear specimen support 420 is then attached to the secondary frame 360 ​​such that the specimen 340 is taut but not stretched. The top plate assembly 200 is closed and fastenably attached to the bladder assembly 180 to form the pressure chamber 140. The bladder of the pressure chamber 140 is inflated to 0.30 psi. The fill points for different diaper sizes are defined in the table below.

[0134] [Table 1]

[0135] In other words, preparation of a sample 340 for analysis by a device 100 incorporating an NMR sensor 160 can be summarized as follows. 1. Prepare sample 340 (e.g., remove / cut cuff, determine fill point, etc.). 2. The NMR sensor 160 is moved away from the invasive application opening 500 located within the top plate assembly 200 to a position located distally from the invasive application opening 500. 3. Open the glass cover by separating the top plate assembly 200 of the pressure chamber 140 from the bladder assembly 180. 4. Insert the sample 340 (absorbent article) by attaching the sample 340 to the front sample support 400 and rear sample support 420, and the attachment means 440 secures the sample 340 to be measured by the device 100 against the bladder assembly 180. 5. Close the top plate assembly 200 by cooperatively associating the top plate assembly 200 with the bladder assembly 180 of the pressure chamber 140. 6. Apply and adjust the pressure applied to the bladder 320 located within the bladder assembly 180 located within the pressure chamber 140 to the desired value (here 0.3 psi).

[0136] In principle, the process for analysis and mapping of fluids in the sample 340 is based on the evaluation of the wetting of the absorbent article to be examined and the fluid distribution in the absorbent article sample 340, using a series of liquid intrusions of given flow parameters. By application of pressure to the bottom of the absorbent article sample 340, the swelling of the absorbent article 340 is directed away from the NMR sensor 160. Thus, the distance between the surface of the absorbent article 340 and the NMR sensor 160 is always kept constant and does not change for different experimental conditions.

[0137] Liquid Application Procedure Two successive insult spurts (see spurt volume / absorbent article length table) are used with a 300 seconds ± 5 seconds pause between successive insults. As shown in Figure 9, when measurements of an insulted sample 340 are performed, the NMR sensor 160 is preferably positioned at a known distance from the insult / spurt center relative to the insult application opening 500 and at a given height from the sample 340 surface.

[0138] The test solution is prepared in 0.9% w / v saline solution prepared by diluting 9.0 g NaCl in 1 L of deionized water. A 2 mM / L solution of diethylenetriaminepentaacetate gadolinium(III) dihydrogen salt (PubChem substance ID 24863829,381667 available from Sigma Aldrich) is added. After addition, the solution is stirred with a shaker at 160 rpm for 1 hour until all crystals are dissolved. Do not use a magnetic bar to stir the solution. The solution is then checked to ensure that no visible undissolved crystals remain. The solution is prepared 10 hours prior to use. The liquid application process can be summarized as follows: 1. Position the NMR sensor 160 adjacent to an intervention application opening 500 located horizontally within the top plate assembly 200 and adjacent to the intervention / ejection area, positioning the NMR sensor 160 as needed from the geographic center of the intervention / ejection core. 2. The NMR sensor 160 is positioned 3500 μm from the top surface of the sample 340 which is in contact engagement with the top plate assembly 200 of the bladder assembly 180. 3. Place the invasive liquid and contrast agent in the deposition assembly 220. 4. Position the deposition assembly 220 against the invasive application opening 500 and the upper surface of the sample 340. 5. Invading the sample 340 with at least a portion of the insulting liquid and contrast agent via the deposition assembly 220. 6. A series of insults / spurts is applied with predetermined parameters (eg, two 40 mL injections, flow rate 10 mL / sec, 300 sec ± 5 sec rest between spurts).

[0139] Profile Testing Process The profiling test is started 300 seconds ± 5 seconds after the liquid application. Profiling gives a signal response to the depth of the sample, which aims to screen samples within a given measurement range (800 μm from the top and bottom). Thus the liquid distribution over different sample layers can be quantified. Profiling is performed at different spots along the length of the sample (at the filling point, 4 cm and 8 cm away from the filling point towards the rear) and a two-dimensional liquid distribution within the sample can finally be obtained by combining the obtained results. An exemplary schematic top view of the three profiling spots used in the study (at the filling point and on the symmetrical line 4 and 8 cm away from the filling point) is shown in Figure 9.

[0140] Program the NMR-MOUSE for a Carr-Purcell-Meiboom-Gill (CPMG) pulse sequence consisting of a 90x pulse followed by a 180y refocusing pulse using the following conditions: Repeat time = 500ms Number of scans = 8 Number of echoes = 8 Resolution=50μm Step size = -50 μm Pulse length = 7.5 μs Echo time = 90 μs Echo shift = 1 μs

[0141] The Rx phase of the NMR signal is optimized during phase adjustment as described by the vendor in order to maximize the real part of the NMR signal used for data processing. In our experiments, a value of 195° was applied. However, the optimal value may vary depending on the NMR instrument used, therefore the Rx phase should be optimized as described by the vendor. The pulse length of the 90° pulse depends on the measurement depth (here it is 6 mm) and was determined to be 7.5 μs based on the optimization procedure described by the vendor. If necessary, the depth can be adjusted using a spacer.

[0142] In other words, the process for performing a profile test process on a sample 340 for analysis by a device 100 incorporating an NMR sensor 160 can be summarized as follows. 1. Translate the NMR sensor 160 to a top position distal to the sample 340 disposed within the bladder assembly 180 until it reaches its outermost vertical position. 2. Move the NMR sensor 160 to its outermost horizontal position located distally from the invasive application opening 500. 3. The deposition assembly 220 is removed from contact engagement with the invasive application opening 500. 4. Move the NMR sensor 160 horizontally (ie, in the y direction) relative to the invasive application opening 500 so that the NMR sensor 160 overlaps with the center of the invasive application opening 500 (ie, at the 0 cm position (ie, at the fill point)). 5. Run the profiling experiment (scan range 0-800 µm, step size 50 µm). 6. Set the NMR sensor 160 to an initial position (800 μm) relative to the top of the sample 340 placed in the bladder assembly 18, and lower the position in 50 μm increments as necessary. 7. Once the experiment is complete, translate the NMR sensor 160 to its outermost vertical (i.e., Z-direction) position. 8. Repeat steps 4-7, placing sensors 4 and 8 cm from the fill point. 9. To measure the specimen from the backsheet side, remove the specimen, attach it to the bladder with the backsheet facing up, and repeat steps 1 to 8.

[0143] Upon completion of the test, the sample 34 can be removed from the device 100 as follows. 1. Translate the NMR sensor 160 vertically (i.e., in the Z direction) to its outermost position. 2. Translate the NMR sensor 160 horizontally (ie, in the y direction) to its outermost horizontal position. 3. Release the pressure applied to bladder 320. 4. Separate the top plate assembly 200 of the pressure chamber 14 from the bladder assembly 180. 5. Remove the sample 340 from the pressure chamber 140. 6. Close the top plate assembly 200 by cooperatively associating the top plate assembly 200 with the bladder assembly 180 of the pressure chamber 140.

[0144] It should be noted that in a typical NMR-MOUSE, the distance between the RF coil of the NMR sensor 160 and the top layer of the sample 340 disposed within the bladder assembly 180 may not be constant during the absorption process due to swelling of the sample 340. It has been found that the use of the bladder assembly 180 in conjunction with the NMR sensor 160 provided as device 100 provides measurements by the NMR sensor 160 that are independent of any swelling that the sample 340 undergoes, since the sample 340 can swell away from the sensitivity slice currently being scanned by the NMR sensor 160.

[0145] To translate the signal amplitude into quantitative information regarding the detected liquid volume, the raw calibration data of the profiling must be correlated with the actual volume of 0.9% saline. The calibration is performed using a liquid mixture of the experimental wetting solution (0.9% saline) and deuterium oxide (DO). Regarding the fact that the NMR test requires the use of a contrast agent, both solutions should be additionally mixed in advance with 2 mM / L of diethylenetriaminepeptin acetate gadolinium(III) dihydrogen salt (PubChem substance ID 24863829, 381667 available from Sigma Aldrich) contrast agent. To prepare the calibration solutions, the DO solution is mixed with the saline solution to obtain 0.9% saline solutions containing 0%, 20%, 80% and 100% contrast agent. The mixtures are shaken and left to stand for at least 12 hours before testing to ensure proper mixing of the components. Add the solution into a glass beaker with an area larger than the NMR sensor area and less than 1 mm thick so that the volume scanned by the NMR device is completely within the measurement range. Carry out a profiling measurement in the area below the surface of the solution. Repeat the procedure for other calibration mixtures to cover all different ratio options. Calculate the area under the graph for each measurement case using the following formula:

[0146]

number

[0147]

number

[0148] Prepare a calibration graph for the given data set and apply a linear fit to obtain the calibration curve equation. Subtract the area under the graph of 100% D2O from each option containing D2O in the mixture. In the considered case, the profiling depth reaches 1.5 mm and the area of ​​the sensor is 3.61 cm 2 (sensor 1.9 x 1.9 cm). Thus, the total volume covered by profiling results in 542 μL for the 0% D2O solution. In case of a miscibility mismatch between D2O and the desired test solution, a one-point calibration (100% solution without D2O) is performed.

[0149] When checking the profile data, the NMR signal is related to the area under the curve of the signal vs. position graph. The area vs. liquid volume correlation is obtained by knowing the integrated area and the volume of saline for each case of the saline content investigated. A calibration curve for the profiling can be derived by checking the linear trend on the graph. The detection and quantification limits (3σ and 9σ, respectively) can be established from the signal-to-noise standard deviation of the sample containing 100% D2O. The raw data (signal amplitude [AU] vs. position [μm]) measured by the NMR-MOUSE must be converted to area values ​​under the graph (area) using equation (1) for a first zone starting from and including the topsheet, extending towards the backsheet, corresponding to 800 μm, and a second zone starting from and including the backsheet, extending towards the topsheet, corresponding to 800 μm. Area values ​​under the graph (area) are also calculated using equation (1) for the profiles measured at 4 cm and 8 cm away from the filling point (Figure 9). However, now the area can be converted to liquid volume using a linear fit using the calibration curve and equation (3).

[0150]

number

[0151] Similarly, a total of three replicate tests are performed for each absorbent article evaluated. For each product, calculate and report the volume (=amount of liquid) for the first and second zones and for the three positions (i.e., 0 cm (=fill point), and 4 cm and 8 cm away from the loading point), and for the sum of the three positions, to the nearest 1 μL, as the arithmetic mean of the replicate tests.

[0152] Air Permeability Test Method All measurements are performed in a laboratory maintained at 23°C ± 2°C and relative humidity 50% ± 2%, and specimens are acclimated to this environment for at least 2 hours prior to testing.

[0153] The air permeability of the substrate is determined according to INDA / EDANA Nonwoven Standard Procedure NWSP070.1.R0(15) using a Textest FX3300 (Textest Instruments, Schwerzenbach, Switzerland) air permeability tester or equivalent. 2 A circular test head having an area of ​​1.0 mm was used to maintain a fixed pressure of 200 Pa across the lower ADS specimen while the airflow through the lower ADS was adjusted to 1.0 cubic meters per square meter (m 2 ) per minute. 3 / m 2The lower ADS is measured in units of airflow / min. When possible, measurements of the lower ADS are made before it is incorporated into an absorbent article. If this is not possible, care should be taken when removing the lower ADS from the product (using Cyto-Freeze, Control Company, Houston, Texas, if necessary) to avoid imparting any contamination or distortion to the test sample layer during removal of material from the other layers. Five rectangular specimens of the lower ADS are taken such that the center of each specimen corresponds to the location of the fill point on the lower ADS and the length and width of each specimen are greater than the smallest dimension of the circular head. The lower ADS specimen is placed under the test head such that the center of the lower ADS specimen coincides with the center of the test head. The five lower ADS specimens are thus analyzed and the air permeability of each is measured to the nearest 1 m. 3 / m 2 m / min 3 / m 2 Record in units per minute. Calculate the arithmetic mean of the individual specimen results and round to the nearest 1m. 3 / m 2 m / min 3 / m 2 Reported as air permeability in / min.

[0154] Opacity Test Method Measurement of opacity by contrast ratio was performed using a standard CIE L spectrophotometer such as a Hunter ColorFlex EZ spectrophotometer (Hunter Associates Laboratory Inc., Reston, Virginia, USA) or its equivalent. * a * b * The color measurements are performed using a suitable 0° / 45° spectrophotometer. The diameter of the measurement port of the instrument is 30 mm. The analysis is performed in a room controlled at approximately 23°C ± 2°C and 50% ± 2% relative humidity.

[0155] Calibrate the instrument according to the vendor's instructions using the standard black and white tile provided by the instrument vendor. After calibration, measure the Y value of the standard white tile and compare it to the true value. The specified true Y value is typically in the range of 83-85 and should differ from the true value by no more than 0.5. Set the spectrophotometer to use the CIE XYZ color space, using D65 standard illuminant and a 10 degree observer.

[0156] When possible, measurements of the lower ADS are taken before it is incorporated into an absorbent article. If this is not possible, care should be taken when removing the lower ADS from the product to avoid imparting any contamination or distortion to the test sample layer during removal of material from the other layers (using Cyto-Freeze, Control Company, Houston, Texas, if necessary). Five rectangular specimens of the lower ADS are taken such that the center of each specimen corresponds to the location of the fill point on the lower ADS, and the length and width of each specimen are greater than the smallest dimension of the head.

[0157] The lower ADS specimen is positioned flat against the instrument with the outward facing surface toward the spectrophotometer's measurement port and the center of the lower ADS specimen (corresponding to the fill point of the lower ADS) coincides with the center of the port. The specimen is further positioned so that there are no tears, holes, or openings in the measurement port. A white standard tile is placed on the opposite surface of the specimen so that it completely covers the portion of the specimen over the measurement port. Take readings of the XYZ values ​​and record each to the nearest 0.01. Without moving the specimen, remove the white plate and replace it with the black standard plate. Take a second reading of the XYZ values ​​and record each to the nearest 0.01.

[0158] Opacity is calculated by dividing the Y value measured using a black tile as a backing by the Y value measured using a white tile as a backing, then multiplying the ratio by 100.

[0159]

number

[0160] Five lower ADS specimens are analyzed in this manner and the opacity of each is recorded. The arithmetic mean of the individual specimen results is calculated and the opacity is reported as a percentage to the nearest 1%.

[0161] Caliper Test Method The caliper of the lower ADS is determined using the caliper test method, in which two flat parallel surfaces are used to apply unidirectional pressure to either side of a substrate specimen and the resulting separation between the parallel surfaces is measured. All measurements are performed in a laboratory maintained at 23°C ± 2°C and 50% ± 2% relative humidity, with specimens acclimated in this environment for at least 2 hours prior to testing.

[0162] Two parallel circular surfaces, 5.6 cm in diameter, are oriented horizontally. When possible, measurements of the lower ADS are made before it is incorporated into an absorbent article. If this is not possible, care must be taken when removing the lower ADS from the product to avoid imparting any contamination or distortion to the test sample layer during removal of material from the other layers (using Cyto-Freeze, Control Company, Houston, Texas, if necessary). Five equivalent rectangular specimens were removed from the lower ADS of five products such that the center of each specimen corresponds to the location of the fill point on the lower ADS and the length and width of each specimen are greater than 5.6 cm. The specimens are then placed between the two parallel circular surfaces, completely covering each of the parallel surfaces and such that the center of the lower ADS specimen coincides with the center of the parallel circular surfaces.

[0163] The parallel surfaces are then brought together at a rate of 3.0±1.0 mm / sec until a pressure of 0.3 psi (2.1 kPa) is achieved, and the separation between the plates is measured and recorded to the nearest 0.01 mm within 2 seconds. The arithmetic mean of the plate separation for the five individual replicate specimens is calculated and reported as the caliper of the substrate in millimeters (mm) to the nearest 0.01 mm under 2.1 kPa.

[0164] One suitable example of an apparatus for use in the caliper method is a Mitutoyo Digimatic Series 543ID-C digital indicator (Mitutoyo America Corp., Aurora, Illinois, USA) or equivalent, with a circular flat "foot" attached to the end of the moving shaft of the indicator gauge. The indicator is mounted horizontally on the granite base, with the shaft of the indicator gauge oriented vertically and the plane of the circular foot parallel to the granite base. The circular foot is sized and weighed such that the gravity force associated with the mass of the foot and the indicator shaft together divided by the area of ​​the circular foot constitutes a downward pressure of 0.3 psi from the circular foot on the granite base. A test specimen at least as large as the circular foot is analyzed between the circular foot and the granite base.

[0165] How to measure horizontal bend drop at 100mm Principle: This method measures the ability of a nonwoven web to bend under its own weight (sometimes called "drapeability"). The measurement principle is to drape a 100 mm piece of material over a sharp 90° edge and measure the vertical drop of this piece of material under its own weight, expressed in mm. This vertical drop is shown as reference number 1 in Figure 15.

[0166] Apparatus: The setup for carrying out the measurements is shown diagrammatically in FIG. (i) A flat support box 2 made of any suitable material such as polycarbonate (e.g., Lexan®), approximately 400 mm long, approximately 200 mm wide and exactly 140 mm high 3 with at least one of its top transverse edges 4 having a sharp 90 degree angle. The box 1 is positioned on a suitable flat surface 5 such as a lab bench; (ii) A movable vertical metal ruler 6 having a stable horizontal foot and calibrated so that its zero corresponds to the flat surface 5 on which the box is placed. The movable vertical metal ruler is used to measure the distance 7 from the hanging edge 8 of the material test specimen 9 to the flat surface.

[0167] Procedure: The measurements are performed at 23°C ± 2°C and 50% ± 2% RH. Unless otherwise specified, all samples should be kept at these conditions for at least 24 hours to equilibrate before carrying out this test. If possible, the measurement of the lower ADS is performed before it is incorporated into the absorbent article. If this is not possible, care should be taken when removing the sample not to impart any contamination or distortion to the test sample layer during removal of material from the other layers (using Cyto-Freeze, Control Company, Houston, Texas, if necessary). A rectangular material specimen 9 having a width of about 80 mm and a length of about 200 mm is cut from the nonwoven roll stock. The length corresponds to the longitudinal direction of the nonwoven web in the absorbent article and the width corresponds to the transverse direction of the nonwoven web in the absorbent article. This method can alternatively be performed on a material specimen having a width of about 50 mm if the width of the original nonwoven is less than 80 mm.

[0168] The material sample 9 is laid flat on any suitable horizontal flat surface, such as a laboratory bench, and a line is drawn across its width exactly 100mm from the leading edge 8 of the material sample.

[0169] The material specimen 9 is then placed on the support box 2 with the first side of the specimen (side A) facing up. As shown in Figure 15, the drawn 100 mm line is positioned exactly on the sharp edge 4 with a 100 mm long portion of the material specimen hanging freely from the support box 2. If necessary, hold a section of the specimen flush with the horizontal side of the sharp edge.

[0170] A movable ruler 6 is positioned near the leading edge 8 of the sagging specimen material so that the distance 7 of the leading edge 8 from the flat surface 5 can be measured. Because the leading edge 8 may not be perfectly horizontal, the distance is measured at two corners of the leading edge 8 as well as at the centre of the leading edge 8 and the arithmetic mean of the three values ​​is recorded to the nearest mm.

[0171] The bend drop 1 is calculated as the difference between the exact height 3 of the drape box (140 mm) and the recorded vertical distance 7 measured with a ruler 6 from the flat surface 5 to the flat surface 5 of the leading edge 8. The above overall procedure is repeated for five similar material specimens. The arithmetic mean of the bend drop values ​​of the five similar material specimens is reported to the nearest mm as the Face A horizontal bend drop at 100 mm.

[0172] The material specimen is then turned upside down (now with side B facing up) and the same procedure as above is performed to obtain the side B horizontal bend drop. The overall recorded horizontal bend drop for the material specimen is the greater of the side A horizontal bend drop and the side B horizontal bend drop.

[0173] Z-Compliance Index and Percentage Recovery Measurement Method Principle: This method measures the ability of a nonwoven web to be compressed in the z-direction under an applied pressure and then recover to its original caliper after the applied pressure is removed.

[0174] Setup: A vertical electronic caliper tester with a circular foot of 40 mm diameter and an accuracy of at least 0.01 mm can be used. The pressure exerted by the foot on the specimen is adjustable via the addition of a preselected weight. Measurements are taken at 0.85 ± 0.05 kPa and 15.4 ± 0.1 kPa.

[0175] Procedure: Measurements are performed at 23°C ± 2°C and 50% ± 2% RH. Unless otherwise specified, all samples should be kept at these conditions for at least 24 hours to equilibrate before performing this test. When possible, measurements of the lower ADS are performed before it is incorporated into an absorbent article. If this is not possible, care should be taken when removing the sample not to impart any contamination or distortion to the test sample layer during removal of material from the other layers (using Cyto-Freeze, Control Company, Houston, Texas, if necessary). The lower ADS specimen is cut from a square sample having a width of approximately 80 mm (or alternatively, in a material specimen having a width of approximately 50 mm if the material is not available in a suitable size).

[0176] The square sample specimen is centered under the caliper foot and the caliper at 0.85±0.05 kPa (P1) is measured and recorded to the nearest 0.01 mm (C1). Without removing the sample from the apparatus, the pressure is increased to 15.4±0.1 kPa (P2) and the caliper is measured and recorded to the nearest 0.01 mm (C2). The pressure can be increased by adding a suitable weight to the caliper foot. Again without moving the sample, the applied pressure is reduced to 0.85±0.05 kPa (e.g., by removing the excess weight) and the caliper is measured a third time (C3) and recorded to the nearest 0.01 mm.

[0177] For the test specimen being measured, the compliance index is Z-Compliance Index=(C1-C2) / (P2-P1) Defined to the nearest 0.1 mm 3 / N will be reported.

[0178] Recovery is, Recovery rate=C3 / C1 * 100% and reported to the nearest 0.1%.

[0179] The above procedure is carried out on five similar specimens of the same nonwoven fabric. The arithmetic mean of the compliance index values ​​among the five specimens is calculated and rounded to the nearest 0.1 mm as the compliance index. 3 Report to the nearest 0.1%. The arithmetic mean of the percent recovery among the five specimens is calculated and reported as percent recovery to the nearest 0.1%.

[0180] Bag stacking height test The stack height of a package of absorbent articles within a bag is measured as follows.

[0181] device A thickness tester is used that has a flat rigid horizontal sliding plate. The thickness tester is configured such that the horizontal sliding plate is free to move vertically while always maintaining a horizontal orientation just above a flat rigid horizontal base plate. The thickness tester includes a device suitable for measuring the gap between the horizontal sliding plate and the horizontal base plate to within +0.5 mm. The horizontal sliding plate and the horizontal base plate are larger than the surface of the absorbent article package that contacts each plate (i.e., each plate extends beyond the contact surface of the absorbent article package in all directions). The horizontal sliding plate applies a downward force of 850±1 grams force (8.34 N) to the absorbent article package, which may be achieved by placing a suitable weight in the center of the top surface of the horizontal sliding plate that does not contact the package, such that the total mass of the sliding plate plus the additional weight is 850±1 grams.

[0182] Test procedure The absorbent article packages are equilibrated at 23±2° C. and 50±2% relative humidity prior to measurement.

[0183] Raise the horizontal sliding plate and center the absorbent article package under the horizontal sliding plate with the absorbent articles in the package oriented horizontally (see Figure 14). Any handles or other packaging mechanisms on the surface of the package that would contact any of the plates should be folded flat against the surface of the package to minimize their effect on the measurement. Slowly lower the horizontal sliding plate until it touches the top surface of the package and then release it. 10 seconds after releasing the horizontal sliding plate, measure the gap between the horizontal plates to within +0.5mm. Measure five identical packages (same size package and same number of absorbent articles) and report the arithmetic average as the package width. Calculate "In-bag stack height" = (package width / number of absorbent articles per stack) x 10 and report to within +0.5mm.

[0184] Altered Fluid Capture Test The Modified Fluid Acquisition (MFA) test is designed to measure the rate at which 0.9% saline is absorbed into an absorbent article compressed at 2.07 kPa. Four doses of known volume are introduced, with each dose beginning 300 seconds ± 5 seconds after the previous dose has been absorbed. The time required to absorb each dose is recorded. All tests are conducted in a room maintained at about 23 ± 2°C and about 50 ± 2% relative humidity. The test fluid is a 0.9% w / v saline solution, which is prepared by weighing 9.0 g ± 0.05 g of NaCl into a weighing boat, transferring it to a 1 L volumetric flask, and diluting to volume with deionized water.

[0185] The MFA device is depicted in Figures 19-12b. The MFA device comprises a rubber bladder assembly 3001 and a top plate assembly 3200 containing a deposition assembly 3100. A controller 3005 is used to 1) monitor impedance across the electrodes 3106 to record the time interval that the 0.9% saline solution is in the cylinder 3102, 2) interface with the liquid pump 3004 to start / stop dispensing, and 3) time the dosing interval. The controller 3005 is capable of recording time events to within ±0.01 seconds. A house air source 3014 is connected to a pressure regulator 3006 capable of delivering air at a suitable flow rate / pressure to maintain 2.07 kPa within the rubber bladder assembly 3001. A liquid pump 3004 (Ismatec MCP-Z gear pump available from Cole Palmer, Vernon Hills, Ill., or equivalent) capable of delivering a flow of 10-80 ml at a flow rate of 3-15 ml / s is attached to the steel tube 3104 of the deposition assembly 3100 via Tygon tubing 3015.

[0186] The rubber bladder assembly 3001 is made of 12.7 mm plexiglass with overall dimensions of 80 cm long, 30 cm wide, and 10 cm high. A manometer 3007 to measure the pressure within the assembly and a pressure gauge 3006 to regulate air admission to the assembly are attached through two holes through the right side. The rubber bladder 3013 is assembled over the box by draping a 50 mm by 100 mm piece of silicone film (0.02 inch thick, 20 Shore A durometer, available from McMaster-Carr, Cleveland, Ohio as part number 86435K85) with enough slack so that the film touches the center point of the bottom of the box. An aluminum frame 3003 with flanges is attached to the top of the film and secured in place using mechanical clamps 3010. When in place, the assembly should be leak-proof at a pressure of 3.45 kPa. Front 3008 and back 3009 sample supports (5 cm x 30 cm x 1 mm) are used to secure the samples. The absorbent article is attached to the top surface of the sample supports using either adhesive tape or mechanical "hook" fasteners. These supports can be adjusted along the length of the aluminum frame 3003 by a simple pin and hole system to accommodate absorbent articles of various sizes and precisely align their fill points.

[0187] The top plate assembly 3200 is made from an 80 cm x 30 cm piece of 12.7 mm plexiglass reinforced with an aluminum frame 3109 for rigidity. The plate has a 170 mm wide x 201 mm long cutout 170 mm forward of the plate 3201 and centered laterally of the plate for mounting the deposition assembly. In addition, the top plate is drilled with 36 3.2 mm diameter holes distributed as shown in FIG. 35A. The holes prevent air from being trapped under the top plate when the rubber bladder is inflated. The top plate assembly 3200 is connected to the rubber bladder assembly 3001 by two hinges 3012. In use, the top assembly is closed over the rubber bladder assembly and locked in place using a mechanical clamp 3011.

[0188] The deposition assembly 3100 is fitted to a top plate 3200 and includes 1) a liquid introduction cylinder 3102, 2) a curved surface 3101 at the fill point of the absorbent article, and 3) an electrode 3106 used to detect fluid within the cylinder 3102. Detailed dimensions of the curved component are shown in Figures 11A-11E. Figure 11A is a side view of the curved component. Figure 11B is an end view of the curved component. Figure 11C is a bottom view of the curved component. Figure 11D is a bottom perspective view of the curved component. Figure 11E is a top perspective view of the curved component. This curved component can be rolled or 3D printed. The top of the introduction cylinder has an outer diameter of 50.8 mm. A plexiglass cylinder 3102 with an inner diameter of 38.1 mm. This fits into the curved component, making the total height of the introduction cylinder 100 mm. The embedded electrodes extend from the connector on the top surface of the curved component and terminate flush with the inner wall of the introduction cylinder, 2 mm from the bottom of the cylinder. The two electrodes are positioned 180 degrees apart. Cut the nylon screen 3107 to fit flush with the bottom of the cylinder to prevent the sample from swelling into the cylinder. Cut a 5 mm semicircle out of the screen in the area adjacent to the two electrodes. Insert the deposition assembly into the top plate as shown in FIG. 12A so that the curved surface fits flush with the bottom of the top plate assembly 3200. Cap the introduction cylinder 3102 with a loose nylon cap 3103. The cap has a 6.35 mm OD steel tube 3104 inserted into its center. When the cap is snapped into place, the bottom of the tube terminates 20 mm above the screen 3107. The cap also has an air hole 3105 to ensure that negative pressure does not impede the absorption rate.

[0189] Prior to testing, all sample articles are conditioned for 2 hours at 23°C ± 2°C and approximately 50% ± 2% relative humidity. First, the absorbent article is prepared by cutting away any inner or outer leg cuffs, waist caps, elastic ears, or side panels, being careful not to affect the topsheet overlying the core region of the article. The absorbent article is laid flat on the lab bench and the intersection of the longitudinal centerline and the size-dependent fill point is identified.

[0190] Fill point, volume, and flow rate for entrapment testing For absorbent articles with a length of 450 mm or less (these are typically size 0, 1 or 2, i.e. small size baby diapers): - Two jets with a waiting time of 300 seconds ± 5 seconds between the end of the first jet and the start of the second jet. -Each squirt has a volume of 40ml. - The filling point is 138mm from the edge of the front waist region (ie waist edge) of the absorbent article. - The flow rate is 8ml / sec.

[0191] For absorbent articles with a length of 450mm or more: - Two jets with a waiting time of 300 seconds ± 5 seconds between the end of the first jet and the start of the second jet. -Each squirt has a volume of 75ml. - The filling point is 102 mm from the edge of the front waist region (ie the waist edge) of the absorbent article. - The flow rate is 15 ml / sec.

[0192] The length and fill point (i.e., their respective distances from the edges of the front waist region of the absorbent article) of the absorbent article are determined when all elastic strands (such as leg elastics) that prevent the flattened configuration are cut and therefore de-elasticized, and the absorbent article is laid flat. The length is determined along the longitudinal centerline. The front end of the absorbent article is attached, topsheet-side up, to the top surface of the front sample plate 3008 using either adhesive tape or mechanical "hook" fasteners. With this arrangement, only the chassis (and not the absorbent core) overlaps the plate. The sample plate 3008 is attached to the aluminum frame 3003 such that, when the top plate assembly is closed, the size-dependent fill point (as defined in Table 2) of the absorbent article is centered longitudinally and laterally within the cylinder 3102. The back end of the absorbent article is secured to the back sample plate 3009 by either adhesive tape or mechanical "hook" fasteners, again such that only the chassis, and not the absorbent core, overlaps the plate. The back sample plate 3009 is then attached to the aluminum frame 3003 so that the article is taunted but not stretched. The top plate assembly is closed and clamped and the rubber bladder is inflated to 2.07 kPa ± 0.07 kPa. The pressure is maintained at this level throughout the filling sequence of the test.

[0193] The pump 3004 is primed and subsequently calibrated to deliver a size-dependent volume and flow rate selected from Table 2. The volume and flow rate should be within ±2% of the target. The cap 3103 is fitted onto the cylinder 3102. The controller 3005 is started, which delivers an initial dose of 0.9% saline solution. After this volume is absorbed, the controller waits 5.0 minutes before adding the next dose. This cycle is repeated for a total of four doses. If any fluid leaks out or around the article (i.e., is not absorbed by the article), the test is stopped. The test is also stopped if the capture time exceeds 1200 seconds. The capture time is defined as the difference between the start time (i.e., when the 0.9% saline is first introduced into the cylinder and the conducting fluid completes the circuit between the electrodes) and the stop time (i.e., when the fluid is completely expelled from the cylinder and the circuit between the electrodes is broken). The controller records the capture time of each dose to the nearest second. After the last dose is obtained, pressure is applied for an additional 10 minutes. The pressure relief valve 3016 is opened to deflate the rubber bladder and then the sample is removed from the capture system.

[0194] Similarly, a total of four replicate tests are performed for each absorbent article evaluated. Acquisition times (seconds) for each dose are calculated to the nearest second and reported as the arithmetic mean of the replicates. EXAMPLES

[0195] Numerous materials for the lower ADS and several absorbent article constructions were tested. Additionally, many absorbent articles currently available on the market were investigated as comparative examples of the present invention.

[0196] Comparative Example: Commercially available baby diapers Pampers Cruisers(TM), USA Huggies Diamond™, USA Pampers Ichiban(TM), Japan Baby Love™, purchased in Germany Goo.N(TM), purchased in China Merries(TM), purchased in China Lelch™, purchased in China

[0197] All products tested were taped diapers (i.e., not pants) that were commercially available in the first half of 2019. Both Pampers diapers have an absorbent core that does not contain any airfelt (the absorbent material is all superabsorbent polymer particles), while all other diapers had absorbents with superabsorbent polymer particles mixed with airfelt.

[0198] The diapers were subjected to NMR MOUSE testing to determine the amount of liquid in the first and second zones.

[0199] [Table 2]

[0200] [Table 3]

[0201] [Table 4]

[0202] [Table 5]

[0203] Examples of the present invention The lower acquisition and distribution layer was added to some of the commercially available diapers described above, and the diapers were subjected to the NMR MOUSE test to determine the amount of liquid in the first and second zones.

[0204] The following materials were used as the lower ADS, ie, the materials were added between the backsheet and the absorbent core.

[0205] Bottom ADS Option 1: Carded air-through bonded nonwoven web made of 60% by weight of 2.2 dtex CoPET / PET solid circular bicomponent (core / sheath) staple fibers and 40% by weight of 3.3 dtex PET solid circular monocomponent staple fibers. The material is 30 g / m 2 The sheet had a basis weight of 1.0 g.

[0206] Bottom ADS Option 2: Carded air-through bonded nonwoven web made of 100% polyethylene / PET solid circular bicomponent (core / sheath) staple fibers of 4.4 dtex. The material is 60 g / m 2 The sheet had a basis weight of 1.0 g.

[0207] Bottom ADS Option 3: Air-through bonded nonwoven web made of 60% by weight of 2.2 dtex CoPET / PET solid circular bicomponent (core / sheath) staple fibers and 40% by weight of 3.3 dtex PET solid circular monocomponent staple fibers. The material is 60 g / m 2 The sheet had a basis weight of 1.0 g.

[0208] Bottom ADS Option 4: A hydroentangled nonwoven web comprising 30% by weight viscose fibers and 70% by weight polyester fibers. The nonwoven web has a density of 40 g / m 2 The sheet had a basis weight of 1.0 g.

[0209] Bottom ADS Option 5: A nonwoven web made of 100% monocomponent PP with an SMS layer. The spunbond ("S") layer has fibers of 2.2 dtex and the meltblown ("M") layer has fiber diameters of less than 2 microns. The meltblown layer has a fiber diameter of 1.8 g / m 2 and each of the spunbond layers has a basis weight of 9.1 g / m 2 The nonwoven web has a basis weight of 20 g / m 2 The sheet had a basis weight of 1.0 g.

[0210] Bottom ADS Option 6: Spunbond nonwoven web made of crimped PP / PP fibers. The nonwoven is hydroentangled. The nonwoven has a density of 35 g / m 2 The sheet had a basis weight of 1.0 g.

[0211] Example, size 4 Sample preparation: For modified Pampers Cruisers (Size 4): The topsheet, upper ADS, and absorbent core (i.e., the layer of absorbent material surrounded by upper and lower substrate layers) of Pampers Cruisers diapers, size 4, commercially available in the United States in the first half of 2019, were carefully removed using ice spray. The original absorbent core was carefully set aside, and the original topsheet and upper ADS were discarded. For each diaper, the lower ADS was removed using a 5 g / m 2 The lower ADS was attached to the wearer-facing surface of the backsheet with a spirally applied hot melt adhesive with a basis weight of 5 g / m2. The lower ADS had a width of 90 mm and was centered on the backsheet in the transverse direction. The lower ADS had the same length as the original absorbent core and was located in the same position as the original absorbent core in the longitudinal direction. The original absorbent core was then removed by applying a 5 g / m2 hot melt adhesive to the absorbent core such that the absorbent core was located exactly in the position before removal. 2 The lower ADS was attached to the lower ADS with a spirally applied hot melt adhesive with a basis weight of 5 g / m 2. In other words, the front end of the lower ADS corresponded with the front end of the absorbent core. The upper ADS, having a length of 360 mm, was then attached to the lower ADS with a basis weight of 5 g / m 2. The upper ADS was laterally centered on the absorbent core and longitudinally spaced 18 mm rearward from the front edge of the absorbent core. 2 The upper ADS was attached to the absorbent core with a spiral applied hot melt adhesive with a basis weight of 30 g / m. The upper ADS had a width of 90 mm and included a top layer made of an air-through bonded nonwoven web made of a mixture of 60% by weight of 2.2 dtex CoPET / PET solid circular bicomponent (core / sheath) staple fibers and 40% by weight of 3.3 dtex PET solid circular monocomponent staple fibers. The top layer of the upper ADS had a basis weight of 30 g / m. 2 The upper ADS had a width of 80 mm and further comprised a lower layer made of crosslinked cellulose fibers. The lower layer of the upper ADS had a basis weight of 170 g / m 2 The paper had a basis weight of 5 g / m 2Both layers of the upper ADS were attached to each other using hot melt adhesive applied in stripes with a basis weight of 1. The top and bottom layers of the upper ADS were centered on each other transversely and such that the front edges of the top and bottom layers of the upper ADS coincided.

[0212] Finally, the spunbond nonwoven web produced on a forming belt as described in WO 2017 / 105997 A1 was subjected to a 5 g / m 2 The nonwoven web forming the topsheet was attached to the upper ADS as a topsheet with a spirally applied hot melt adhesive at a basis weight of 25 g / m. The nonwoven web forming the topsheet comprised continuous bicomponent polypropylene / polypropylene (side-by-side) fibers and had a basis weight of 25 g / m. 2 Upon formation on the forming belt, the nonwoven web had areas of high and low basis weight.

[0213] The diaper samples were compressed into a flexible bag with an in-bag stack height, i.e., 85 mm total caliper of 10 bifold diapers, for one week. The bag was then opened and the diapers removed from the bag were conditioned at 23°C + / - 2°C and 50% + / - 10% relative humidity (RH) for at least 24 hours prior to any testing.

[0214] For modified Merries (size 4): The commercial topsheet, upper ADS and absorbent core (i.e., the layer of absorbent material encased by the upper and lower substrate layers) of a size 4 Merries diaper commercially available in Japan in the first half of 2019 were carefully removed as one laminate using ice spray. For each diaper, 5 g / m 2 The lower ADS was attached to the wearer-facing surface of the backsheet with a spirally applied hot melt adhesive with a basis weight of 5 g / m2. The lower ADS had a width of 90 mm and was centered on the backsheet in the transverse direction. The lower ADS had the same length as the original absorbent core and was positioned in the same position as the original absorbent core in the longitudinal direction. The laminate formed by the original absorbent core, the upper ADS and the topsheet was then glued with a 5 g / m2 adhesive so that the absorbent core was positioned exactly in its pre-removal position. 2The lower ADS was attached to the lower ADS with a spirally applied hot melt adhesive having a basis weight of 1.0 g / m2, in other words, the front end of the lower ADS corresponded with the front end of the absorbent core.

[0215] The diaper samples were compressed into a flexible bag with an in-bag stack height, i.e., 90 mm total caliper of 10 bifold diapers, for one week. The bag was then opened and the diapers removed from the bag were conditioned at 23°C + / - 2°C and 50% + / - 10% relative humidity (RH) for at least 24 hours prior to any testing.

[0216] For modified Pampers Ichiban (size 4): The commercial topsheet, upper ADS and absorbent core (i.e., the layer of absorbent material encased by upper and lower substrate layers) of a Pampers Ichiban diaper size 4 that was commercially available in China in the first half of 2019 were carefully removed using ice spray. The original absorbent core was carefully set aside and the original topsheet and upper ADS were disposed of. For each diaper, 5 g / m 2 The lower ADS was attached to the wearer-facing surface of the backsheet with a spirally applied hot melt adhesive with a basis weight of 5 g / m2. The lower ADS had a width of 90 mm and was centered on the backsheet in the transverse direction. The lower ADS had the same length as the original absorbent core and was located in the same position as the original absorbent core in the longitudinal direction. The original absorbent core was then removed by applying a 5 g / m2 hot melt adhesive to the backsheet such that the absorbent core was located exactly in the position before removal. 2 The lower ADS was attached to the lower ADS with a spirally applied hot melt adhesive with a basis weight of 5 g / m 2 . In other words, the front end of the lower ADS corresponded with the front end of the absorbent core. The upper ADS, having a length of 360 mm, was then attached to the lower ADS with a basis weight of 5 g / m 2 . The upper ADS was laterally centered on the absorbent core and longitudinally spaced 18 mm from the front edge of the absorbent core. 2The upper ADS was attached to the absorbent core with a spiral applied hot melt adhesive with a basis weight of 30 g / m. The upper ADS had a width of 90 mm and included a top layer made of an air-through bonded nonwoven web made of 60% by weight of 2.2 dtex CoPET / PET solid circular bicomponent (core / sheath) staple fibers and 40% by weight of 3.3 dtex PET solid circular monocomponent staple fibers. The top layer of the upper ADS had a basis weight of 30 g / m. 2 The upper ADS also contained a lower layer having a width of 80 mm and made of crosslinked cellulose fibers. The lower layer of the upper ADS had a basis weight of 170 g / m 2 The paper had a basis weight of 5 g / m 2 Both layers of the upper ADS were attached to each other using hot melt adhesive applied in stripes with a basis weight of 1. The top and bottom layers of the upper ADS were centered on each other transversely and such that the front edges of the top and bottom layers of the upper ADS coincided.

[0217] Finally, the spunbond nonwoven web produced on a forming belt as described in WO 2017 / 105997 A1 was subjected to a 5 g / m 2 The topsheet was attached to the upper ADS with a hot melt adhesive applied in a spiral configuration with a basis weight of 25 g / m. The topsheet nonwoven web contained bicomponent continuous polypropylene / polypropylene (side-by-side) fibers and had a weight of 25 g / m. 2 Upon formation on the forming belt, the nonwoven web had areas of high and low basis weight.

[0218] The diaper samples were compressed into a flexible bag with an in-bag stack height, i.e., 90 mm total caliper of 10 bifold diapers, for one week. The bag was then opened and the diapers removed from the bag were conditioned at 23°C + / - 2°C and 50% + / - 10% relative humidity (RH) for at least 24 hours prior to any testing.

[0219] [Table 6]

[0220] Example, Size 2 Modified Pampers Ichiban, size 2; Run 1: The commercial topsheet, upper ADS, and absorbent core of a Pampers Ichiban diaper size 2 commercially available in China in the first half of 2019 were carefully removed using ice spray. The original absorbent core was carefully set aside and the original topsheet and upper ADS were disposed of. For each diaper, 5 g / m 2 The lower ADS was attached to the wearer-facing surface of the backsheet with a spirally applied hot melt adhesive with a basis weight of 5 g / m2. The lower ADS had a width of 90 mm and was centered on the backsheet in the transverse direction. The lower ADS had the same length as the original absorbent core and was located in the same position as the original absorbent core in the longitudinal direction. The original absorbent core was then removed by applying a 5 g / m2 hot melt adhesive to the backsheet such that the absorbent core was located exactly in the position before removal. 2 The lower ADS was attached to the lower ADS with a spirally applied hot melt adhesive with a basis weight of 5 g / m 2. In other words, the front end of the lower ADS corresponded with the front end of the absorbent core. The upper ADS, having a length of 350 mm, was then attached to the lower ADS with a basis weight of 5 g / m 2. In other words, the front end of the lower ADS corresponded with the front end of the absorbent core. The upper ADS ... 2 The upper ADS was attached to the absorbent core with a spiral applied hot melt adhesive with a basis weight of 30 g / m. The upper ADS had a width of 90 mm and included a top layer made of an air-through bonded nonwoven web made of 60% by weight of 2.2 dtex CoPET / PET solid circular bicomponent (core / sheath) staple fibers and 40% by weight of 3.3 dtex PET solid circular monocomponent staple fibers. The top layer of the upper ADS had a basis weight of 30 g / m. 2 The upper ADS also contained a lower layer having a width of 80 mm and made of crosslinked cellulose fibers. The lower layer of the upper ADS had a basis weight of 110 g / m 2 The paper had a basis weight of 5 g / m 2 The top and bottom layers of the upper ADS were attached to each other using hot melt adhesive applied in stripes with a basis weight of 1. The top and bottom layers of the upper ADS were centered relative to each other transversely and such that the front edges of the top and bottom layers of the upper ADS were coincident.

[0221] Finally, a spunbond nonwoven web having monocomponent polypropylene fibers was used as the top sheet and hot melt adhesive was applied at 5 g / m 2 The topsheet nonwoven web was spirally applied with a basis weight of 12 g / m 2 The diaper samples were compressed into a bag with an in-bag stack height, i.e., 100 mm total caliper of 10 bifold diapers, for one week. The bag was then opened and the diapers removed from the bag were conditioned at 23°C + / - 2°C and 50% + / - 10% relative humidity (RH) for at least 24 hours prior to any testing.

[0222] Modified Pampers Ichiban, size 2; Run 2: For Run 2, the same procedure was followed as described above for Run 1, except that the material of the upper ADS was different. The upper ADS in Run 2 was a bi-layer material, where the upper layer of the upper ADS in direct contact with the topsheet was a carded, air-through bonded nonwoven web of polyethylene / polypropylene bicomponent fibers, weighing 20 g / m 2 The bottom layer of the upper ADS, which was in direct contact with the upper substrate layer of the absorbent core, had a basis weight of 60 g / m2 made of 3% by weight latex, 20% by weight polypropylene / PET bicomponent fibers, and 77% by weight cellulose fibers. 2 The upper ADS was 80 g / m 2 The total basis weight was 1.01 g.

[0223] Comparative Example I without Lower ADS: Modified Pampers Ichiban, Size 2 The commercial topsheet and upper ADS of a Pampers Ichiban diaper, size 2, which was commercially available in China in the first half of 2019, were carefully removed using ice spray, and the original topsheet and upper ADS were disposed of. The upper ADS, having a length of 350 mm, was then coated with 5 g / m 2 glycerin, 10 ... 2The upper ADS was attached to the absorbent core with a spirally applied hot melt adhesive with a basis weight of 140 g / m. The upper ADS included a top layer having a width of 90 mm and was made of the same material as that used as option 1 for the lower ADS in other examples herein. The upper ADS also included a bottom layer having a width of 80 mm and made of crosslinked cellulose fibers. The bottom layer of the upper ADS was 140 g / m 2 The paper had a basis weight of 5 g / m 2 The top and bottom layers of the upper ADS were attached to each other using hot melt adhesive applied in a stripe pattern with a basis weight of 1. The top and bottom layers of the upper ADS were centered relative to each other transversely and such that the front edges of the top and bottom layers of the upper ADS were coincident.

[0224] Finally, a spunbond nonwoven web having monocomponent polypropylene fibers was used as the top sheet and hot melt adhesive was applied at 5 g / m 2 The topsheet nonwoven web was spirally applied with a basis weight of 12 g / m 2 The diaper samples were compressed into a bag with an in-bag stack height, i.e., 100 mm total caliper of 10 bifold diapers, for one week. The bag was then opened and the diapers removed from the bag were conditioned at 23°C + / - 2°C and 50% + / - 10% relative humidity (RH) for at least 24 hours prior to any testing.

[0225] Comparative Example II without Lower ADS: Modified Pampers Ichiban, Size 2: The top layer of the upper ADS is a 30 g / m2 woven fabric made of 60% by weight of 2.2 dtex CoPET / PET solid circular bicomponent (core / sheath) staple fibers and 40% by weight of 3.3 dtex PET solid circular monocomponent fibers. 2 The bottom layer of the upper ADS was made of crosslinked cellulose fibers and had a basis weight of 110 g / m 2 The sheet had a basis weight of 1.0 g.

[0226] 12g / m 2 A spunbond nonwoven web made of monocomponent polypropylene fibers having a basis weight of 100 g was used as the topsheet.

[0227] All other sample preparation steps, dimensions and configuration of the samples were identical to Comparative Example I above.

[0228] Comparative Example III without Lower ADS: Modified Pampers Swaddlers, Size 2. The product design of this example is similar to Pampers Swaddlers diapers, size 2, marketed in North America in the first half of 2019, with the following modifications described below. The absorbent material or superabsorbent weighed 6.6 grams and followed the same distribution as the marketed product. The top layer of the upper ADS was made of the same material used in the marketed product, with a length of 288 mm and a width of 105 mm. The top layer of the upper ADS was placed 31 mm away from the front edge of the absorbent core. The bottom layer of the upper ADS was made of the same material used in the marketed product, with a length of 268 mm and a width of 80 mm. The bottom layer of the upper ADS was placed 10 mm away from the front edge of the top layer of the upper ADS. The backsheet was made of 5 g / m 2 30 g / m2 attached to the backsheet film with a slot-applied hot melt adhesive at a basis weight of 2 It is made of a spunlaid hydroentangled web.

[0229] The diaper samples were compressed into a bag with an in-bag stack height, i.e., 100 mm total caliper of 10 bifold diapers, for one week. The bag was then opened and the diapers removed from the bag were conditioned at 23°C + / - 2°C and 50% + / - 10% relative humidity (RH) for at least 24 hours prior to any testing.

[0230] [Table 7]

[0231] [Table 8]

[0232] Examples with and without a sub-substrate layer beneath the layer of absorbent material To compare absorbent articles in which a lower substrate layer is provided between the absorbent article layer and the lower ADS (as are all of the inventive examples above) with absorbent articles in which the lower ADS is in direct contact with the garment-facing surface of the layer of absorbent material, one of the examples above (Pampers Ichiban, size 2, run 1 with lower ADS option 2) was modified such that the lower substrate layer was removed. The results are shown in Table 8. Another example was made by replacing the lower substrate layer of Comparative Example III with Lower ADS option 6.

[0233] [Table 9]

[0234] [Table 10]

[0235] Dimensions and values ​​disclosed herein should not be understood as being strictly limited to the exact numerical values ​​recited. Instead, unless otherwise indicated, each such dimension is intended to mean both the recited value and a functionally equivalent range surrounding that value. For example, a dimension disclosed as "40 mm" is intended to mean "about 40 mm."

[0236] All documents cited herein, including any cross-referenced or related patents or patent applications, and any patent applications or patents to which this application claims priority or benefit, are incorporated herein by reference in their entirety, unless expressly stated to the contrary. The citation of any document shall not be deemed to be prior art to any invention disclosed or claimed herein, or to teach, suggest or disclose such invention, either alone or in combination with any other reference(s). Furthermore, to the extent that any meaning or definition of a term in this document conflicts with any meaning or definition of the same term in a document incorporated by reference, the meaning or definition assigned to that term in this document shall govern.

[0237] While particular embodiments of the present invention have been illustrated and described, it would be obvious to those skilled in the art that various other changes and modifications can be made without departing from the spirit and scope of the invention. It is therefore intended to cover in the appended claims all such changes and modifications that are within the scope of this invention.

Claims

1. An absorbent article (20) comprising a front waist region, a rear waist region, and a crotch region located between the front waist region and the rear waist region, a topsheet (24), a backsheet (26) and a layer of absorbent material (28) sandwiched between said topsheet (24) and said backsheet (26), said layer of absorbent material (28) comprising a superabsorbent polymer; a lower acquisition and distribution system (60) having at least one nonwoven or woven layer, said lower acquisition and distribution system (60) being sandwiched between said layer of absorbent material (28) and said backsheet (26), said absorbent article (20) having a first zone starting from and including said topsheet (24) and extending towards said backsheet (26), corresponding to 800 μm; and a second zone starting from and including said backsheet (26), extending towards said topsheet (24), corresponding to 800 μm; The absorbent article (20) is subjected to the NMR MOUSE method described herein to determine and sum the amount of liquid at three defined locations, the absorbent article (20) having a total liquid amount of less than 90 μl in the first zone and a total liquid amount of less than 80 μl in the second zone, the three defined locations being at a liquid fill point, a point 4 cm away from the fill point towards the rear waist region on the longitudinal centerline, and a point 8 cm away from the fill point towards the rear waist region on the longitudinal centerline, the total liquid amount being the sum of the liquid amounts measured at each of the three defined locations corresponding to a measured area of ​​1.9 cm x 1.9 cm and a measured depth of 800 μm.

2. 10. The absorbent article of claim 1, wherein the amount of liquid at the fill point in said second zone is 50 μl or less as measured by the NMR MOUSE test method described herein.

3. 3. The absorbent article of claim 1 or 2, wherein the amount of liquid at the fill point in said first zone is 50 μl or less as measured by the NMR MOUSE test method described herein.

4. 4. The absorbent article of any one of claims 1 to 3, further comprising an upper acquisition and distribution system (50) having at least one layer, said upper acquisition and distribution system (50) being sandwiched between said layer of absorbent material (28) and said topsheet (24).

5. The absorbent article (20) of any one of claims 1 to 4, wherein the lower acquisition and distribution system (60) comprises a nonwoven fabric, and the nonwoven fabric contained in the lower acquisition and distribution system (60) is a nonwoven web selected from the group consisting of air-through bonded nonwoven fabrics made of staple fibers, spunlaced nonwoven fabrics made of staple fibers, air-through bonded nonwoven fabrics made of spunlaid fibers, and spunlaced nonwoven fabrics made of spunlaid fibers.

6. The absorbent article (20) of any one of claims 1 to 5, wherein the lower acquisition and distribution system (60) comprises a nonwoven fabric comprising fibers, the fibers of the nonwoven fabric comprised in the lower acquisition and distribution layer (60) comprising at least 30% by weight of crimped fibers based on the total weight of the nonwoven fabric comprised in the lower acquisition and distribution layer, and the crimped fibers have a two-dimensional crimp, a three-dimensional crimp, or a combination of two-dimensional and three-dimensional crimp.

7. The absorbent article (20) according to any one of claims 1 to 6, wherein the nonwoven fabric included in the lower acquisition and distribution system (60) is made of polyethylene terephthalate (PET), co-PET, polypropylene, polyethylene, polylactic acid (PLA), polyhydroxyalkaloid (PHA), or combinations or mixtures thereof.

8. The lower acquisition and distribution system (60) is 150 m 3 / m 2 The absorbent article (20) of any one of claims 1 to 7, having an air permeability of greater than 1 / min.

9. The absorbent article (20) of any one of the preceding claims, wherein said absorbent article has a total acquisition time of less than 120 seconds when measured according to the test methods described herein.

10. The absorbent article (20) according to any one of the preceding claims, wherein the thickness of said lower acquisition and distribution system (60) is between 0.1 and 2.0 mm.

11. The absorbent article (20) according to any one of the preceding claims, wherein said lower acquisition and distribution system (60) consists of a single layer of nonwoven web.

12. 12. The absorbent article (20) of any one of claims 1 to 11, wherein the layer of absorbent material (28) is partially or completely surrounded by and in direct contact with an upper substrate layer (45) and a lower substrate layer (46), the upper substrate layer (45) being between the layer of absorbent material (28) and an upper acquisition and distribution system (50), and the lower substrate layer (46) being between the layer of absorbent material (28) and the lower acquisition and distribution system (60).

13. 13. The absorbent article of claim 12, wherein the lower acquisition and distribution system (60) and the lower substrate layer (46) are selected from the group consisting of: a) the lower acquisition and distribution system (60) is hydrophobic and the lower substrate layer (46) is hydrophilic; b) the lower acquisition and distribution system (60) and the lower substrate layer (46) are both hydrophilic, the lower acquisition and distribution system being less hydrophilic than the lower substrate layer (46); and c) the lower acquisition and distribution system (60) and the lower substrate layer (46) are both hydrophobic and the lower substrate layer (46) is less hydrophobic than the lower acquisition and distribution system (60).

14. 12. The absorbent article (20) of any one of claims 1 to 11, wherein the layer of absorbent material (28) and the lower acquisition and distribution system (60) are partially or completely surrounded by and in direct contact with an upper substrate layer (45) and a lower substrate layer (46), the upper substrate layer (45) being between the layer of absorbent material (28) and the upper acquisition and distribution system (50), the lower substrate layer (46) being between the lower acquisition and distribution system (60) and the backsheet, and the layer of absorbent material (28) being in direct contact with the lower acquisition and distribution system (60).

15. The absorbent article (20) according to any one of claims 1 to 11, wherein the layer of absorbent material (28) is partially or completely surrounded by and in direct contact with the upper substrate layer (45) and the lower acquisition and distribution system (60), the upper substrate layer (45) being between the layer of absorbent material (28) and the upper acquisition and distribution system (50).

16. The absorbent article (20) according to any one of the preceding claims, wherein the surface of the lower acquisition and distribution system (60) facing the wearer and / or garment has a three-dimensional surface and a layer adjacent to the surface having the three-dimensional surface has a flat two-dimensional surface.

17. The absorbent article (20) of any one of the preceding claims, wherein said backsheet (26) is breathable.

18. The absorbent article (20) according to any one of the preceding claims, wherein said absorbent article has a length of more than 450mm.

19. The absorbent article (20) according to any one of the preceding claims, wherein said absorbent article has a length of 450mm or less.

20. The lower acquisition and distribution system (60) is 4 mm 3 / N, The compliance index is Compliance index=(C1−C2) / (P2−P1) is defined as P1 is 0.85±0.05 kPa; P2 is 15.4±0.1 kPa; C1 is the thickness of the sample specimen when pressure P1 is applied to the sample specimen; C2 is the thickness of the sample specimen when the pressure is increased from P1 to P2; An absorbent article (20) according to any one of the preceding claims.

21. The absorbent article (20) according to any one of the preceding claims, wherein said lower acquisition and distribution system (60) has a horizontal bend drop of greater than 60 mm.

22. the lower acquisition and distribution system (60) having a recovery percentage greater than 50; The recovery percentage is Recovery percentage = C3 / C1*100 is defined as P1 is 0.85±0.05 kPa; P2 is 15.4±0.1 kPa; C1 is the thickness of the sample specimen when pressure P1 is applied to the sample specimen; C3 is the thickness of the sample specimen when the pressure is increased from P1 to P2 and then reduced to P1; An absorbent article (20) according to any one of the preceding claims.

Citation Information

Patent Citations

  • Dispersion strip for absorbent products

    JP2003524485A

  • Absorbent article

    JP2015066377A

  • Absorbent article having a liquid direction conversion layer

    JP2018531142A